Magnetic tape, magnetic tape cassette and magnetic recording and reproducing apparatus
Patent Information
- Application Number
- CN202580022538.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]根据本发明的一方式,能够提供一种PES的变动少的磁带。并且,根据本发明的一方式,能够提供一种包括该磁带的磁带盒及磁记录再现装置。
Smart Images

Figure CN123023100A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a magnetic tape, a magnetic tape cassette, and a magnetic recording and reproducing apparatus. Background Technology
[0002] Magnetic tape is widely used as a recording medium for recording various types of data (see, for example, Patent Document 1 and Patent Document 2). Previous technical documents Patent documents
[0003] Patent Document 1: Japanese Patent Application Publication No. 2006-96850 Patent Document 2: Japanese Patent Application Publication No. 2021-106070 Summary of the Invention The technical problem to be solved by the invention
[0004] To date, magnetic tape development has progressed by balancing ensuring the smoothness of the magnetic layer surface to improve electromagnetic conversion characteristics with reducing the coefficient of friction relative to the magnetic head. The smoothness and frictional characteristics of the magnetic layer surface have been designed according to the electromagnetic conversion characteristics required by each generation of drives. However, with each generation, recording capacity has increased exponentially, leading not only to increased linear recording density but also to increased track density in the width direction of the tape, thus requiring increasingly narrower widths for the playback elements of the magnetic head. Therefore, in recent years, there has been a demand for more accurate positioning of the magnetic head in the width direction of the tape.
[0005] To determine the position of the magnetic head along the width of the magnetic tape, a servo pattern is recorded on the tape. By reading the servo pattern, the position of the magnetic head can be accurately determined. By moving the magnetic head up and down according to the servo pattern, data can be recorded and reproduced at the target position. However, sometimes the up-and-down movement of the magnetic head cannot keep up with the changes in the servo pattern. As an indicator of this tracking, the PES (Position Error Signal) value is known. To improve the tape travel stability, it is preferable to suppress the variation of this PES value below a certain level.
[0006] To date, in order to suppress PES variation, as described in Patent Document 1 (Japanese Patent Application Publication No. 2006-96850), efforts have been made to minimize the coefficient of friction between the magnetic layer surface and each sliding component, and as described in Patent Document 2 (Japanese Patent Application Publication No. 2021-106070), efforts have been made to minimize the coefficient of friction against the magnetic head. To date, as described in Patent Documents 1 and 2, PES variation can be suppressed simply by pursuing low friction. However, as the track density increases, PES variation tends to occur; therefore, to cope with further increases in track density, it is desirable to further suppress PES variation.
[0007] One aspect of the present invention is to provide a magnetic tape with minimal PES variation. means for solving technical problems
[0008] Through repeated research, the inventors concluded that as track density increases, the correlation between the magnetic tape's tracking ability and the PES (Pulse Equivalent) of the guide rollers positioned before and after the magnetic head in a magnetic recording and playback device (commonly referred to as a "drive") becomes particularly important. Furthermore, through further in-depth research, the inventors discovered that variations in PES can be suppressed by setting the standard deviation of the frictional force, as detailed below, within the following range.
[0009] One aspect of the present invention is described below. (1) A magnetic tape having a non-magnetic support and a magnetic layer containing strongly magnetic powder, wherein, The standard deviation of the friction force determined by measuring the friction force between the surface of the aforementioned magnetic layer and the guide roller of the LTO (Linear Tape-Open) driver is greater than 0.35 N (Newtons) and less than 0.70 N. (2) The magnetic tape according to (1), wherein, The area ratio (hereinafter also referred to as "SEM bright area ratio above 140 nm") of multiple bright regions with an equivalent circle diameter of 140 nm or more in the binarized image of the secondary electron image of the surface of the magnetic layer obtained by scanning electron microscopy (SEM) at an accelerating voltage of 5 kV is 0.010% or more and 0.100% or less. (3) The magnetic tape according to (1) or (2), wherein, The standard deviation of the above frictional force is above 0.45N and below 0.70N. (4) The magnetic tape according to any one of (1) to (3), wherein, The vertical rectangularity ratio of the aforementioned magnetic tape is 0.65 or higher. (5) The magnetic tape according to any one of (1) to (4), wherein, Between the aforementioned non-magnetic support and the aforementioned magnetic layer, there is also a non-magnetic layer containing non-magnetic powder. (6) The magnetic tape according to any one of (1) to (5), wherein, The non-magnetic support has a back coating containing non-magnetic powder on the side opposite to the side with the magnetic layer. (7) The magnetic tape according to any one of (1) to (6), wherein, The total thickness of the aforementioned magnetic tape is less than 5.0 μm. (8) The magnetic tape according to any one of (1) to (7), wherein, The aforementioned non-magnetic support is a polyester support. (9) The magnetic tape according to any one of (1) to (8), wherein, The aforementioned strong magnetic powder is hexagonal ferrite powder. (10) The magnetic tape according to (9), wherein, The aforementioned hexagonal ferrite powder is hexagonal barium ferrite powder. (11) The magnetic tape according to (9), wherein, The aforementioned hexagonal ferrite powder is hexagonal strontium ferrite powder. (12) The magnetic tape according to (1), wherein, In the binarized image of the secondary electron image obtained by scanning electron microscopy at an accelerating voltage of 5 kV on the surface of the aforementioned magnetic layer, the area fraction of multiple bright regions with an equivalent circle diameter of 140 nm or more is 0.010% or more and 0.100% or less. The standard deviation of the above-mentioned frictional force is above 0.45N and below 0.70N. The vertical aspect ratio of the aforementioned magnetic tape is 0.65 or higher. Between the aforementioned non-magnetic support and the aforementioned magnetic layer, there is also a non-magnetic layer containing non-magnetic powder. On the surface of the non-magnetic support opposite to the surface with the magnetic layer, there is also a back coating containing non-magnetic powder. The total thickness of the aforementioned magnetic tape is less than 5.0 μm. The aforementioned non-magnetic support is a polyester support. The aforementioned strong magnetic powder is selected from the group consisting of hexagonal barium ferrite, hexagonal strontium ferrite powder and ε-iron oxide powder. (13) A magnetic tape cassette comprising any one of (1) to (12) a magnetic tape. (14) A magnetic recording and reproducing apparatus comprising any one of (1) to (12) a magnetic tape. Invention Effects
[0010] According to one aspect of the present invention, a magnetic tape with minimal PES variation can be provided. Furthermore, according to another aspect of the present invention, a magnetic tape cassette including the magnetic tape and a magnetic recording and playback apparatus can be provided. Attached Figure Description
[0011] Figure 1 This is a schematic diagram (a plan view of the state viewed from the side) of a roll-to-roll measuring instrument used to measure the friction of guide rollers. Figure 2 It means Figure 1 A schematic diagram of a portion of the measuring instrument shown. Detailed Implementation
[0012] [Cassette tape] One aspect of the present invention relates to a magnetic tape having a non-magnetic support and a magnetic layer containing strongly magnetic powder. The standard deviation of the frictional force, determined by measuring the frictional force between the surface of the magnetic layer and the guide roller of an LTO driver, is 0.35 N or more and 0.70 N or less. Hereinafter, the standard deviation of the frictional force will also be referred to as "standard deviation of guide roller frictional force".
[0013] <Standard deviation of guide roller friction> In this invention and this specification, the "standard deviation of guide roller friction force" is determined by the following method under an environment with a temperature of 20-25°C and a relative humidity of 40-60%. Figure 1 This is a schematic diagram (a plan view of the state viewed from the side) of a roll-to-roll measuring instrument used to measure the friction of guide rollers. Figure 2 It means Figure 1 The diagram shows a partial schematic of the measuring instrument. Hereinafter, the two rollers located closer to the guide rollers will be referred to as "rollers (upper part)" and the other two rollers will be referred to as "rollers (lower part)". exist Figure 1 In this process, the magnetic tape MT is fed out from the feed roller 1, passes through the lower roller 7 and the upper roller 5, and is positioned so that the magnetic layer surface of the magnetic tape MT contacts the guide roller 3. It then passes through the upper roller 6 and the lower roller 8, and is wound up by the take-up roller 2. This constitutes one pass. The length of each pass is set to 20m. In this invention and specification, "the surface of the magnetic layer" has the same meaning as the magnetic layer side surface of the magnetic tape. As guide rollers, LTO-driven guide rollers are used. An LTO-driven drive refers to a drive conforming to the LTO standard. Specifically, guide rollers disassembled from an IBM TS-1160 tape drive are used. The guide rollers are thoroughly cleaned with ethanol and dried before use. As guide rollers, a new (i.e., unused) guide roller is used each time the tape being tested (one sample) is measured. For a total of 400 tape runs as described below, the same guide rollers are used without changing them. Figure 2 The length "L" shown is the distance from the centerline of guide roller 3 to the centerlines of rollers 5 and 6 respectively. Both L's are the same length. Guide roller 3 is referenced to a direction parallel to the length L, with a wrap angle (...). Figure 2In the middle, angle "a") is set to 0.75° between guide rollers 5 and 6, and the length (L×2) between guide rollers 5 and 6 is set to be more than 150 mm and less than 300 mm. Regarding the wrap angle, the position of the magnetic tape surface without guide rollers is set to 0 mm. If guide roller 3 is pressed into the distance L[mm]×tan0.75°[mm] between the center line of guide roller 3 and the center lines of each guide roller 5 and 6, the wrap angle can be adjusted to 0.75°. A tension of 0.8 N is applied to the magnetic tape MT, and the acceleration is set to 2 m / s. 2 The conveyor speed is set to 4 m / s, and the magnetic tape MT is fed. Friction force is acquired every 2 milliseconds. The friction force applied to the guide roller 3 is converted into voltage by the strain gauge 4. The relationship between the voltage and the load of the strain gauge 4 is pre-adjusted. In one pass, the standard deviation of the friction force acquired at 5-15 m of passing is calculated for each pass. Therefore, the number of friction force data per pass is approximately 1250. A total of 400 passes are conducted. The arithmetic mean of the standard deviations of the friction force acquired in a total of 200 passes within the range of 200 to 400 passes is taken as the standard deviation of the guide roller friction force of the magnetic tape being measured. In the above measurements, considering that the LTO standard is capable of handling the high-density recording of recent years, LTO drive guide rollers were used. However, the magnetic tapes mentioned above are not limited to those used in LTO drives. These magnetic tapes can be used for data recording and / or playback in LTO drives, as well as in drives other than LTO drives.
[0014] The inventors believe that the standard deviation of the guide roller friction force can serve as an indicator of the magnetic tape's following ability on the guide roller. If the standard deviation of the magnetic tape's guide roller friction force is 0.35 N or more, the following ability on the guide roller is excellent, thus suppressing variations in PES (Polarization of Surface Equivalents). Specifically, it is speculated that if the standard deviation of the guide roller friction force is 0.35 N or more, the generation of slippage and / or friction between the magnetic tape and the guide roller can be suppressed. The standard deviation of the guide roller friction force is preferably 0.40 N or more, more preferably 0.45 N or more, and even more preferably 0.50 N or more. On the other hand, a standard deviation of guide roller friction force of 0.70 N or less can also help improve the following of the guide roller to suppress PES variation. This is presumably because if the standard deviation of guide roller friction force is 0.70 N or less, the adhesion of the magnetic tape to the guide roller can be suppressed. The standard deviation of guide roller friction force can also be, for example, 0.69 N or less, 0.68 N or less, or 0.67 N or less.
[0015] <Surface area ratio of bright areas above 140nm in SEM> The inventors believe that improving the tracking performance of the guide rollers can help suppress PES (Polarization of Surface Area) variations. On the other hand, practically speaking, a low coefficient of friction between the magnetic tape and the magnetic head is preferable. Methods known include coarsening the surface roughness of the magnetic layer and increasing the number of surface protrusions to reduce the coefficient of friction to the magnetic head. However, it can be inferred that there is a trade-off between the tracking performance of the guide rollers and the pursuit of low friction characteristics. Through repeated and in-depth research, the inventors have discovered that this trade-off can be resolved by controlling the surface area ratio of bright areas above 140 nm in SEM, as determined by the method described below.
[0016] The "surface area ratio of bright areas above 140nm in SEM" in this invention and this specification is obtained by the following method. In this invention and specification, the scanning electron microscope used to determine the surface area ratio of bright areas above 140 nm in SEM is a field emission scanning electron microscope (FE-SEM). For example, the FE-SEM S4800 manufactured by Hitachi, Ltd. can be used as an FE-SEM. The magnetic layer surface was not coated on the magnetic tape before the SEM images were taken. The SEM images captured are secondary electron images. The equivalent diameter of a circle is defined as the value obtained by rounding to one decimal place and discarding the second and subsequent decimal places, using a scale of 1 nm. In determining the number of bright areas, only a portion of them are included in the binarized image, while the remaining bright areas outside the binarized image are excluded from the measurement. Secondary electron images of the magnetic layer surface of the magnetic tape being measured were captured using FE-SEM. The imaging conditions were set to an accelerating voltage of 5 kV, a working distance of 5 mm, and a magnification of 9,000x. During imaging, an un-imaged area on the magnetic layer surface was selected, and the focus was adjusted under the above conditions to capture the secondary electron image. Parts displaying dimensions (micrometer scales, crosshairs, etc.) were removed from the captured image to obtain a secondary electron image with 960 pixels × 1280 pixels. The above operation was performed 10 times on different parts of the magnetic layer surface of the magnetic tape of the test object. The acquired secondary electronic image is then read into image processing software and binarized according to the following steps. Image analysis software, such as the free software ImageJ, can be used. Through binarization, the image is separated into bright areas (white parts) and dark areas (black parts). The threshold used for binarizing the secondary electron images acquired above is set with a lower limit of 210 gray levels and an upper limit of 255 gray levels. Binarization is performed using these two thresholds. After binarization, noise removal is performed using image analysis software. Noise removal can be performed, for example, by using the Despeckle denoising algorithm in ImageJ to remove noise. The binarized image obtained in this way is used to determine the number of bright regions (i.e., white areas) and the area of each bright region using image analysis software. The equivalent circle diameter of each bright region is then calculated based on its area. Specifically, the equivalent circle diameter L is calculated using the calculated area A, and then by using 2 × (A / π)^(1 / 2) = L. Here, the operator "^" represents exponentiation. The above steps are performed on the binarized images (10 images) obtained above. For all bright regions with an equivalent circle diameter of 140 nm or more in each binarized image, calculate the area ratio (percentage) of each bright region A relative to the total area of the image (i.e., the total area of the image at a magnification of 9,000). The sum of these calculated area ratios is taken as the area ratio of the multiple bright regions with an equivalent circle diameter of 140 nm or more in the binarized image. The above-obtained binarized images (10 images) are subjected to a process of calculating the area ratio of multiple bright regions with an equivalent circle diameter of 140 nm or more, and their arithmetic mean is used as the area ratio of multiple bright regions with an equivalent circle diameter of 140 nm or more for the magnetic tape of the test object (SEM bright surface area ratio of 140 nm or more).
[0017] Magnetic layers are typically formed using a magnetic layer forming composition that includes one or more non-magnetic powders in addition to strongly magnetic powders. The inventors believe that the non-magnetic powders (hereinafter also referred to as "abrasives") contained in the magnetic layer, in order to impart abrasiveness to the surface of the magnetic layer, are observed to be the aforementioned bright areas. Specifically, the bright surface area ratio at SEM 140 nm or higher is considered to be the surface area occupancy of the magnetic layer containing abrasives with a relatively large size of 140 nm or higher equivalent circle diameter. From the viewpoint of eliminating the trade-offs described above, the bright surface area ratio at SEM 140 nm or higher is preferably 0.010% or higher. Specifically, from the viewpoint of suppressing adhesion to the magnetic head, the bright surface area ratio at SEM 140 nm or higher is preferably 0.010% or higher. From this viewpoint, the bright surface area ratio at SEM 140 nm or higher is more preferably 0.012% or higher, and even more preferably 0.015% or higher. Furthermore, from the viewpoint of eliminating the trade-offs described above, the surface area ratio of bright areas above 140nm in SEM is preferably 0.100% or less. More specifically, from the viewpoint of improving the following ability of the guide roller, the surface area ratio of bright areas above 140nm in SEM is preferably 0.100% or less. From this viewpoint, the surface area ratio of bright areas above 140nm in SEM is more preferably 0.060% or less, and even more preferably 0.050% or less.
[0018] The inventors believe that the following is a method for controlling the surface area ratio of bright areas above 140nm in SEM. As a method for controlling the surface area ratio of bright areas above 140 nm in SEM within the aforementioned range, one example is adjusting the classification conditions of the abrasive dispersion (hereinafter also referred to as "abrasive liquid"). In the classification, it is preferable to perform a flow cytometry centrifugation process that removes only coarse particles without significantly altering the average particle size distribution of the abrasive dispersion. If the lower limit of the particle size range to be removed is set as D, then in the flow cytometry centrifugation process, the rotational speed of the cylinder is changed according to Stokes' formula to adjust the gravitational acceleration, thereby enabling the removal of abrasive particles with a particle size of D or larger. In this way, abrasive particles within the desired particle size range (i.e., particle size D or larger) can be removed. By using an abrasive dispersion that has undergone centrifugation in this manner, the surface area ratio of bright areas above 140 nm in SEM can be controlled relatively easily without changing the amount of abrasive itself added. For example, regarding abrasives, please refer to paragraphs 0030 to 0032 of Japanese Patent Application Publication No. 2004-273070. As an abrasive, it is preferable to use an abrasive with a specific surface area (hereinafter referred to as "BET specific surface area") of 17 m², as determined by the BET (Brunauer-Emmett-Teller) method. 2 / g or more and 40m 2The abrasive content of the magnetic layer is less than / g. The abrasive content relative to 100.0 parts by weight of the strongly magnetic powder can, for example, be more than 1.0 parts by weight and less than 10.0 parts by weight. For example, by adjusting the abrasive size, the abrasive grading conditions (specifically, the centrifugation conditions), and the abrasive content in the composition for forming the magnetic layer, the surface area ratio of bright areas above 140nm in SEM can be controlled within the range described above.
[0019] The following is a more detailed explanation of the aforementioned magnetic tape.
[0020] <Magnetic Layer> (Strongly magnetic powder) As the strongly magnetic powder contained in the magnetic layer, one or more strongly magnetic powders known for use in the magnetic layers of various magnetic recording media can be used in combination. From the viewpoint of improving recording density, it is preferable to use a strongly magnetic powder with a small average particle size. Considering this, the average particle size of the strongly magnetic powder is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, even more preferably 35 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, and still even more preferably 20 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the strongly magnetic powder is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, even more preferably 15 nm or more, and even more preferably 20 nm or more.
[0021] Hexagonal ferrite powder Hexagonal ferrite powder is a preferred specific example of a strongly magnetic powder. For details regarding hexagonal ferrite powder, see, for example, paragraphs 0012-0030 of Japanese Patent Application Publication No. 2011-225417, paragraphs 0134-0136 of Japanese Patent Application Publication No. 2011-216149, paragraphs 0013-0030 of Japanese Patent Application Publication No. 2012-204726, and paragraphs 0029-0084 of Japanese Patent Application Publication No. 2015-127985.
[0022] In this invention and specification, "hexagonal ferrite powder" refers to a strongly magnetic powder whose crystal structure as a hexagonal ferrite can be detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs. For example, if the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs to the crystal structure of a hexagonal ferrite, then the crystal structure of the hexagonal ferrite is determined to be the main phase. If only a single structure is detected by X-ray diffraction analysis, that detected structure is considered the main phase. The crystal structure of a hexagonal ferrite contains at least iron atoms, divalent metal atoms, and oxygen atoms as constituent atoms. Divalent metal atoms refer to metal atoms that can become divalent cations as ions, such as strontium atoms, barium atoms, calcium atoms, and lead atoms. In this invention and specification, "hexagonal strontium ferrite powder" refers to a hexagonal ferrite in which the predominant divalent metal atom is strontium, and "hexagonal barium ferrite powder" refers to a hexagonal ferrite in which the predominant divalent metal atom is barium. The predominant divalent metal atom refers to the divalent metal atom that occupies the largest proportion of the divalent metal atoms in the powder, based on an atomic percentage. Rare earth atoms are not included in the aforementioned divalent metal atoms. In this invention and specification, "rare earth atoms" are selected from the group consisting of scandium (Sc), yttrium (Y), and lanthanides. The lanthanide atoms are selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).
[0023] The following is a more detailed description of hexagonal strontium ferrite powder as one type of hexagonal ferrite powder.
[0024] The activation volume of hexagonal strontium ferrite powder is preferably in the range of 800–1600 nm. 3 Within the aforementioned range, micronized hexagonal strontium ferrite powder with an activation volume within this range is suitable for manufacturing magnetic tapes that exhibit excellent electromagnetic conversion properties. The preferred activation volume of the hexagonal strontium ferrite powder is 800 nm. 3 The above, for example, could also be 850nm. 3 That's all. Furthermore, from the viewpoint of further improving electromagnetic conversion characteristics, the activation volume of hexagonal strontium ferrite powder is more preferably 1500 nm. 3 Hereinafter, 1400nm is further preferred. 3 The following is a further preferred option: 1300nm 3The following is a further preferred option: 1200nm 3 Hereinafter, 1100nm is further preferred. 3 The activation volume of hexagonal barium ferrite powder is also the same.
[0025] "Activation volume" is a unit of magnetization reversal and an indicator of the magnetic strength of a particle. The activation volume and anisotropy constant Ku described in this invention and specification were determined using a vibrating sample type magnetometer at a magnetic field scanning speed of 3 minutes and 30 minutes (measurement temperature: 23℃±1℃) using the coercivity Hc measuring unit, and calculated according to the following relationship between Hc and activation volume V. The unit of the anisotropy constant Ku is 1 erg / cc = 1.0 × 10⁻⁶. -1 J / m 3 . Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2} In the above formula, Ku: anisotropy constant (unit: J / m) 3 Ms: saturation magnetization (kA / m), k: Boltzmann constant, T: absolute temperature (K), V: activation volume (cm³) 3 A: Spin precession frequency (unit: s) -1 ), t: magnetic field reversal time (unit: s)
[0026] An anisotropy constant Ku can be cited as an indicator of reduced thermal fluctuations (in other words, improved thermal stability). Hexagonal strontium ferrite powder preferably has a Ku value of 1.8 × 10⁻⁶. 5 J / m 3 The above-mentioned Ku, more preferably, can have 2.0 × 10 5 J / m 3 The above refers to the Ku value. Furthermore, the Ku value of hexagonal strontium ferrite powder can, for example, be 2.5 × 10⁻⁶. 5 J / m 3 However, a higher Ku value generally indicates higher thermal stability and is therefore preferred; therefore, it is not limited to the values exemplified above.
[0027] Hexagonal strontium ferrite powder may or may not contain rare earth atoms. When hexagonal strontium ferrite powder contains rare earth atoms, it is preferable that the rare earth atoms are contained at a content of 0.5 to 5.0 atomic% (bulk content) relative to 100 atomic% of iron atoms. In one embodiment, the hexagonal strontium ferrite powder containing rare earth atoms may exhibit rare earth atom segregation on the surface layer. In this invention and this specification, "rare earth atom surface layer bias" refers to the ratio of the rare earth atom content relative to 100 atomic percent of iron atoms in the solution obtained by partially dissolving hexagonal strontium ferrite powder with acid (hereinafter, "rare earth atom surface layer content" or rare earth atoms are simply referred to as "surface layer content") to the rare earth atom content relative to 100 atomic percent of iron atoms in the solution obtained by completely dissolving hexagonal strontium ferrite powder with acid (hereinafter, "rare earth atom bulk content" or rare earth atoms are simply referred to as "bulk content"). The ratio of rare earth atom surface layer content to rare earth atom bulk content is greater than 1.0. The meaning of the rare earth atom content of hexagonal strontium ferrite powder described later is the same as the meaning of rare earth atom bulk content. In contrast, since partial dissolution using acid dissolves only the surface portion of the particles constituting hexagonal strontium ferrite powder, the rare earth atom content in the solution obtained through partial dissolution refers to the rare earth atom content in the surface portion of the particles constituting the hexagonal strontium ferrite powder. A rare earth atom surface portion content ratio satisfying "rare earth atom surface portion content / rare earth atom bulk content > 1.0" indicates that rare earth atoms are concentrated in the surface portion (i.e., present in greater quantities than in the interior) of the particles constituting the hexagonal strontium ferrite powder. In this invention and specification, the surface portion refers to a region extending from the surface of the particles constituting the hexagonal strontium ferrite powder towards the interior.
[0028] When hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atom content (bulk content) relative to 100 atomic% of iron atoms is preferably in the range of 0.5 to 5.0 atomic%. It is believed that containing rare earth atoms at a bulk content within the above range, with the rare earth atoms clustered in the surface layer of the particles constituting the hexagonal strontium ferrite powder, helps to suppress the decrease in reproduction output during repeated reproduction. This is presumably because including rare earth atoms at a bulk content within the above range and with the rare earth atoms clustered in the surface layer of the particles constituting the hexagonal strontium ferrite powder increases the anisotropy constant Ku. A higher value of the anisotropy constant Ku further suppresses the phenomenon known as thermal fluctuation (in other words, it improves thermal stability). By suppressing thermal fluctuations, the decrease in reproduction output during repeated reproduction can be suppressed. It is speculated that the segregation of rare earth atoms in the surface layer of hexagonal strontium ferrite powder particles helps to stabilize the spin of iron (Fe) sites in the lattice of the surface layer, thereby increasing the anisotropy constant Ku. From the viewpoint of further suppressing the reduction of reproduction output when repeated reproduction, the rare earth atom content (bulk content) is more preferably in the range of 0.5 to 4.5 atomic%, more preferably in the range of 1.0 to 4.5 atomic%, and even more preferably in the range of 1.5 to 4.5 atomic%.
[0029] The above-mentioned bulk content rate is the content rate obtained by completely dissolving hexagonal strontium ferrite powder. In this invention and this specification, unless otherwise specified, the content rate for atoms refers to the bulk content rate obtained by completely dissolving hexagonal strontium ferrite powder. As rare earth atoms, the hexagonal strontium ferrite powder containing rare earth atoms may contain only one type of rare earth atom or may contain two or more types of rare earth atoms. The above-mentioned bulk content rate when containing two or more rare earth atoms is calculated based on the sum of the two or more rare earth atoms. This also applies to other components in this invention and this specification. That is, unless otherwise specified, a component may use only one type or two or more types. The content or content rate when using two or more types refers to the sum of the two or more types.
[0030] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atoms contained can be any one or more of the rare earth atoms. From the viewpoint of further suppressing the reduction of reproduction output during repeated reproduction, preferred rare earth atoms include neodymium atoms, samarium atoms, yttrium atoms, and dysprosium atoms, more preferably neodymium atoms, samarium atoms, and yttrium atoms, and even more preferably neodymium atoms.
[0031] In hexagonal strontium ferrite powder exhibiting rare-earth atom segregation on the surface, the rare-earth atoms only need to be segregated on the surface of the particles constituting the hexagonal strontium ferrite powder, and the degree of segregation is not limited. For example, regarding hexagonal strontium ferrite powder exhibiting rare-earth atom segregation on the surface, the ratio of the surface content of rare-earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare-earth atoms obtained by complete dissolution under the dissolution conditions described later, "surface content / bulk content", exceeds 1.0, and can be 1.5 or more. A "surface content / bulk content" greater than 1.0 indicates that rare-earth atoms are segregated on the surface of the particles constituting the hexagonal strontium ferrite powder (i.e., their presence is greater than that in the interior). Furthermore, the ratio of the surface portion content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described later, "surface portion content / bulk content", can be, for example, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. However, in hexagonal strontium ferrite powder with rare earth atom surface portion segregation, the rare earth atoms only need to be segregated in the surface portion of the particles constituting the hexagonal strontium ferrite powder, and the above-mentioned "surface portion content / bulk content" is not limited to the upper or lower limit shown.
[0032] The partial and complete dissolution of hexagonal strontium ferrite powder will be described below. For hexagonal strontium ferrite powder existing in powder form, the partially and completely dissolved sample powders are collected from the same batch of powder. On the other hand, for hexagonal strontium ferrite powder contained in the magnetic layer of a magnetic tape, a portion of the hexagonal strontium ferrite powder removed from the magnetic layer is used for partial dissolution, and another portion is used for complete dissolution. The removal of the hexagonal strontium ferrite powder from the magnetic layer can be performed, for example, by the method described in paragraph 0032 of Japanese Patent Application Publication No. 2015-91747. The aforementioned partial dissolution refers to the point at which dissolution is complete, to the point where it is visually identifiable that hexagonal strontium ferrite powder remains in the liquid. For example, partial dissolution can dissolve 10-20% by mass (with the total number of particles as 100% by mass) of the particles constituting the hexagonal strontium ferrite powder. On the other hand, the aforementioned complete dissolution refers to the point at which dissolution is complete, to the point where it is no longer visually identifiable that hexagonal strontium ferrite powder remains in the liquid. The determination of partial dissolution and surface layer content mentioned above is performed, for example, by the following method. However, the dissolution conditions, such as the amount of sample powder described below, are merely examples, and any dissolution conditions capable of partial and complete dissolution can be used. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 1 mol / L hydrochloric acid is kept on a hot plate at a set temperature of 70 °C for 1 hour. The resulting solution is filtered through a 0.1 μm membrane filter. Elemental analysis of the filtrate is performed using an inductively coupled plasma (ICP) analyzer. This allows the determination of the surface portion content of rare earth atoms relative to 100 atomic percent of iron atoms. In cases where multiple rare earth atoms are detected by elemental analysis, the total content of all rare earth atoms is taken as the surface portion content. This is also applied to the determination of bulk content. On the other hand, the determination of complete dissolution and bulk content is carried out, for example, by the following method. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 4 mol / L hydrochloric acid is kept on a hot plate at a set temperature of 80 °C for 3 hours. Then, the same procedure as the determination of partial dissolution and surface content is performed to determine the bulk content relative to 100 atomic% of iron atoms.
[0033] From the viewpoint of improving the reproduction output when reproducing data recorded on magnetic tape, it is preferable to have a higher mass magnetization σs of the strongly magnetic powder contained in the magnetic tape. In this regard, hexagonal strontium ferrite powder containing rare-earth atoms but lacking rare-earth atom surface segregation tends to show a significant decrease in σs compared to hexagonal strontium ferrite powder without rare-earth atoms. Therefore, in terms of suppressing this significant decrease in σs, hexagonal strontium ferrite powder with rare-earth atom surface segregation is also considered preferable. In one embodiment, the σs of the hexagonal strontium ferrite powder can be 45 A·m. 2 / kg or above, or 47A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, σs is preferably 80 A·m. 2 / kg or less, preferably 60A·m 2 / kg or less. σs can be measured using known measuring devices capable of measuring magnetic properties, such as vibrating sample type magnetometers. In this invention and specification, unless otherwise specified, the mass magnetization σs is the value measured with a magnetic field strength of 15 kOe. The conversion factor from Oe (Oersted) to SI unit A / m is 10. 3 / 4π.
[0034] Regarding the atomic content (bulk content) of the hexagonal strontium ferrite powder, the strontium atom content relative to 100 atomic% of iron atoms can, for example, be in the range of 2.0 to 15.0 atomic%. In one embodiment, the hexagonal strontium ferrite powder may contain only strontium atoms as divalent metal atoms in the powder. Furthermore, in another embodiment, the hexagonal strontium ferrite powder may also contain one or more other divalent metal atoms besides strontium atoms. For example, it may contain barium atoms and / or calcium atoms. When it contains divalent metal atoms other than strontium atoms, the barium atom content and calcium atom content in the hexagonal strontium ferrite powder can, for example, be in the range of 0.05 to 5.0 atomic% relative to 100 atomic% of iron atoms.
[0035] As for the crystal structures of hexagonal ferrites, the known types include magnetoplumbleite (also known as "M-type"), W-type, Y-type, and Z-type. Hexagonal strontium ferrite powder can adopt any crystal structure. The crystal structure can be confirmed by X-ray diffraction analysis. Hexagonal strontium ferrite powder can be detected by X-ray diffraction analysis to have a single crystal structure or two or more crystal structures. For example, in one embodiment, hexagonal strontium ferrite powder can be detected by X-ray diffraction analysis to have only an M-type crystal structure. For example, M-type hexagonal ferrite is made from AFe... 12 O 19The composition is represented by the formula. Here, A represents a divalent metal atom. In the case of hexagonal strontium ferrite powder of type M, A is only a strontium atom (Sr), or when A contains multiple divalent metal atoms, as mentioned above, the strontium atom (Sr) accounts for the largest proportion on an atomic percentage basis. The divalent metal atom content of hexagonal strontium ferrite powder is usually determined according to the type of crystal structure of hexagonal ferrite and is not particularly limited. The same applies to the iron atom content and oxygen atom content. Hexagonal strontium ferrite powder contains at least iron atoms, strontium atoms, and oxygen atoms, and may also contain rare earth atoms. Moreover, hexagonal strontium ferrite powder may contain atoms other than these atoms, or it may not contain atoms other than these atoms. As an example, hexagonal strontium ferrite powder may contain aluminum atoms (Al). The aluminum atom content relative to 100 atomic% of iron atoms may be, for example, 0.5 to 10.0 atoms. From the viewpoint of further suppressing the decrease in reproduction output during repeated reproduction, hexagonal strontium ferrite powder preferably contains iron atoms, strontium atoms, oxygen atoms, and rare earth atoms, and the content of atoms other than these atoms is 10.0 atomic% or less relative to 100 atomic% of iron atoms, more preferably in the range of 0 to 5.0 atomic%, and may also be 0 atomic%. That is, in one embodiment, hexagonal strontium ferrite powder may not contain atoms other than iron atoms, strontium atoms, oxygen atoms, and rare earth atoms. The content expressed as atomic% is obtained by converting the content of each atom (unit: mass%) obtained by completely dissolving the hexagonal strontium ferrite powder into a value expressed as atomic% using the atomic weight of each atom. Furthermore, in this invention and this specification, for a certain atom, "not containing" means that the content obtained by complete dissolution and measurement by an ICP analyzer is 0 mass%. The detection limit of the ICP analyzer is generally 0.01 ppm (parts per million) or less on a mass basis. The term "excluding" is used to mean including amounts less than the detection limit of the ICP analyzer. In one embodiment, the hexagonal strontium ferrite powder may be free of bismuth atoms (Bi).
[0036] Metal powder As a preferred specific example of a strongly magnetic powder, strongly magnetic metal powder can also be cited. For details regarding strongly magnetic metal powder, please refer to paragraphs 0137 to 0141 of Japanese Patent Application Publication No. 2011-216149 and paragraphs 0009 to 0023 of Japanese Patent Application Publication No. 2005-251351.
[0037] ε-iron oxide powder As a preferred specific example of a strongly magnetic powder, ε-iron oxide powder can be cited. In this invention and this specification, "ε-iron oxide powder" refers to a strongly magnetic powder whose crystal structure of ε-iron oxide is detected as the main phase by X-ray diffraction analysis. For example, if the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs to the crystal structure of ε-iron oxide, it is determined that the crystal structure of ε-iron oxide is detected as the main phase. Methods for manufacturing ε-iron oxide powder include methods using goethite, reverse micelle methods, etc. These manufacturing methods are all well known. Furthermore, regarding methods for manufacturing ε-iron oxide powder in which a portion of Fe is replaced by substituted atoms such as Ga, Co, Ti, Al, Rh, etc., for example, refer to J.Jpn.Soc.Powder Metallurgy Vol.61 Supplement, No S1, pp S280-S284, JMater.Chem.C, 2013, 1, pp.5200-5206, etc. However, the method for manufacturing ε-iron oxide powder, which can be used as a strong magnetic powder in the magnetic layer of the magnetic tape described above, is not limited to the methods listed herein.
[0038] The activation volume of ε-iron oxide powder is preferably in the range of 300–1500 nm. 3 Within the range described above, micronized ε-iron oxide powder exhibiting an activation volume within this range is suitable for manufacturing magnetic tapes that exhibit excellent electromagnetic conversion properties. The preferred activation volume of the ε-iron oxide powder is 300 nm. 3 The above, for example, could also be 500nm. 3 That's all. Furthermore, from the viewpoint of further improving electromagnetic conversion characteristics, the activation volume of ε-iron oxide powder is more preferably 1400 nm. 3 The following is a further preferred option: 1300nm 3 The following is a further preferred option: 1200nm 3 The preferred option is 1100nm. 3 the following.
[0039] An anisotropy constant Ku can be cited as an indicator of reduced thermal fluctuations, or in other words, improved thermal stability. ε-iron oxide powder preferably has a Ku value of 3.0 × 10⁻⁶. 4 J / m 3 The above-mentioned Ku, more preferably, can have 8.0 × 10 4 J / m 3 The above refers to the Ku. Furthermore, the Ku of ε-iron oxide powder can, for example, be 3.0 × 10⁻⁶. 5 J / m 3 However, a higher Ku value indicates higher thermal stability and is therefore preferred; it is not limited to the values exemplified above.
[0040] From the viewpoint of improving reproduction output when reproducing data recorded on magnetic tape, it is preferable that the magnetic tape contains strongly magnetic powder with a high mass magnetization σs. In this regard, in one embodiment, the σs of ε-iron oxide powder can be 8 A·m. 2 / kg or above, or 12A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, the σs of ε-iron oxide powder is preferably 40 A·m. 2 Below / kg, preferably 35A·m 2 / kg or less.
[0041] Unless otherwise specified in this invention and specification, the average particle size of various powders, such as strongly magnetic powders, is the value determined using a transmission electron microscope by the following method. The powder was photographed using a transmission electron microscope at a magnification of 100,000, and then printed on photographic paper or displayed on a monitor at a total magnification of 500,000 to obtain photographs of the particles constituting the powder. Target particles were selected from the obtained particle photographs, and their outlines were traced using a digitizer to determine the size of the particles (primary particles). Primary particles refer to unaggregated, independent particles. The above measurements were performed on 500 randomly selected particles. The arithmetic mean of the particle sizes of these 500 particles was taken as the average particle size of the powder. For example, a Hitachi H-9000 transmission electron microscope can be used as the transmission electron microscope described above. Furthermore, the particle size can be measured using known image analysis software, such as Carl Zeiss KS-400 image analysis software. Unless otherwise specified, the average particle size described in the following examples section refers to the value measured using a Hitachi H-9000 transmission electron microscope as the transmission electron microscope and Carl Zeiss KS-400 image analysis software as the image analysis software. In this invention and specification, "powder" refers to a collection of multiple particles. For example, strongly magnetic powder refers to a collection of multiple strongly magnetic particles. Furthermore, the collection of multiple particles is not limited to the particles constituting the collection being in direct contact, but also includes the presence of binders, additives, etc., between the particles, as described later. The term "particle" is sometimes also used to refer to powder.
[0042] As a method for collecting sample powder from magnetic tape to determine particle size, the method described in paragraph 0015 of Japanese Patent Application Publication No. 2011-048878 can be used, for example.
[0043] Unless otherwise specified in this invention and specification, the size of the particles constituting the powder (particle size) refers to the shape of the particles observed in the aforementioned particle photographs. (1) In the cases of needle-like, spindle-shaped, and columnar shapes (where the height is greater than the maximum major diameter of the base), the length of the major axis constituting the particle is used, i.e., the length of the major axis. (2) In the case of a plate or column (where the thickness or height is less than the maximum major diameter of the plate surface or bottom surface), the maximum major diameter of the plate surface or bottom surface shall be used. (3) In cases where the shape is spherical, polyhedral, irregular, etc., and the major axis of the constituent particles cannot be determined based on the shape, the equivalent circle diameter shall be used. The equivalent circle diameter is the diameter obtained by the circular projection method.
[0044] Furthermore, the average aspect ratio of the powder refers to the arithmetic mean of the values obtained from the above measurements of the minor axis length of the particles, i.e., the minor axis length, and the (major axis length / minor axis length) of each particle. Here, unless otherwise specified, the so-called minor axis length, in the definition of particle size above (1), refers to the length of the minor axis constituting the particle; similarly, in (2), it refers to the thickness or height; and in (3), since there is no difference between the major axis and the minor axis, for convenience, (major axis length / minor axis length) is regarded as 1. Furthermore, unless otherwise specified, when the particles have a specific shape, for example, in the case of the above definition of particle size (1), the average particle size is the average major axis length; in the case of the above definition of particle size (2), the average particle size is the average plate diameter; and in the case of the above definition of particle size (3), the average particle size is the average diameter (also referred to as the average particle size).
[0045] The content (filling rate) of the strongly magnetic powder in the magnetic layer is preferably in the range of 50 to 90% by mass relative to the total mass of the magnetic layer, and more preferably in the range of 60 to 90% by mass. From the viewpoint of increasing recording density, a high filling rate of the strongly magnetic powder in the magnetic layer is preferred.
[0046] (Adhesive) The aforementioned magnetic tape can be a coated magnetic tape and may contain an adhesive in the magnetic layer. The adhesive refers to one or more resins. Various resins commonly used as adhesives in coated magnetic recording media can be used as adhesives. For example, resins selected from polyurethane resins, polyester resins, polyamide resins, vinyl chloride resins, acrylic resins copolymerized from styrene, acrylonitrile, methyl methacrylate, etc., cellulose resins such as nitrocellulose, epoxy resins, phenoxy resins, polyvinyl acetal, polyvinyl butyral, etc., can be used alone or in mixtures. Among these, polyurethane resins, acrylic resins, cellulose resins, and vinyl chloride resins are preferred. These resins can be homopolymers or copolymers. These resins can also be used as adhesives in the non-magnetic layer and / or back coating layer described later. For more information on the above adhesives, please refer to paragraphs 0028 to 0031 of Japanese Patent Application Publication No. 2010-24113. Furthermore, the adhesive can also be a radiation-curable resin such as an electron beam-curable resin. For information on radiation-curable resins, please refer to paragraphs 0044 to 0045 of Japanese Patent Application Publication No. 2011-048878. The average molecular weight of the resin used as a binder, based on its weight-average molecular weight, can be, for example, 10,000 or more and 200,000 or less. The weight-average molecular weight used in this invention and specification refers to a value obtained by converting a value measured by gel permeation chromatography (GPC) under the following testing conditions to polystyrene. The weight-average molecular weight described in the Examples section below is a value obtained by converting a value measured under the following testing conditions to polystyrene. The binder can be used in amounts of, for example, 1.0 to 30.0 parts by weight relative to 100.0 parts by weight of the strongly magnetic powder. GPC Unit: HLC-8120 (Manufactured by TOSOH CORPORATION) Column: TSK gel Multipore HXL-M (manufactured by TOSOH CORPORATION, 7.8mm ID (Inner Diameter) × 30.0cm) Eluent: Tetrahydrofuran (THF)
[0047] (Curing agent) The curing agent can also be used together with a resin that can be used as an adhesive. Regarding the curing agent, in one approach, it can be a compound that undergoes a curing reaction (crosslinking reaction) by heating (i.e., a thermosetting compound); in another approach, it can be a photocurable compound that undergoes a curing reaction (crosslinking reaction) by light irradiation. The curing agent undergoes a curing reaction in the magnetic layer forming process, and at least a portion of it can be contained in the magnetic layer in a state where it has reacted (crosslinked) with other components such as the adhesive. This is also true for layers formed using the composition containing the curing agent when it is used to form other layers. A thermosetting compound is preferred as the curing agent, and polyisocyanate is preferred. For details regarding polyisocyanate, please refer to paragraphs 0124-0125 of Japanese Patent Application Publication No. 2011-216149. In the composition for forming the magnetic layer, from the viewpoint of improving the strength of the magnetic layer, it is preferable to use a curing agent in an amount of 50.0-80.0 parts by weight, for example, 0-80.0 parts by weight relative to 100.0 parts by weight of the adhesive, to use the curing agent.
[0048] (additive) The magnetic layer may contain one or more additives as needed. Commercially available additives may be selected based on the desired properties. Alternatively, compounds synthesized by known methods may be used as additives. Additives may be used in any amount. Examples of additives include the aforementioned curing agent. Furthermore, examples of additives included in the magnetic layer include non-magnetic powders (e.g., inorganic powders, carbon black), lubricants, dispersants, dispersing aids, antifungal agents, antistatic agents, and antioxidants. Regarding dispersants, see paragraphs 0061 and 0071 of Japanese Patent Application Publication No. 2012-133837. Dispersants may also be added to the composition for forming a non-magnetic layer. Regarding dispersants that can be added to the composition for forming a non-magnetic layer, see paragraph 0061 of Japanese Patent Application Publication No. 2012-133837. Furthermore, examples of non-magnetic powders that can be included in the magnetic layer include non-magnetic powders that can function as abrasives and non-magnetic powders that can function as protrusion-forming agents to form appropriately protruding protrusions on the surface of the magnetic layer (e.g., non-magnetic colloidal particles). The average particle size of the protrusion-forming agent is preferably in the range of 30 to 200 nm, and more preferably in the range of 50 to 100 nm. Regarding abrasives, as described above.
[0049] Fatty acids, fatty acid esters, fatty acid amides The magnetic tape described above can contain one or more components selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in the magnetic layer side portion on the non-magnetic support. This magnetic layer side portion may contain only one component selected from fatty acids, fatty acid esters, and fatty acid amides, or it may contain two or three components. Furthermore, as fatty acids, it may contain only one or two or more fatty acids. This also applies to fatty acid esters and fatty acid amides. In this invention and specification, the term "magnetic layer side portion on the non-magnetic support" refers to the magnetic layer for magnetic tapes having a magnetic layer directly on a non-magnetic support, and to both the magnetic layer and / or non-magnetic layer for magnetic tapes having a non-magnetic layer (described later) between the non-magnetic support and the magnetic layer. "Magnetic layer side portion on the non-magnetic support" is also simply referred to as "magnetic layer side portion." The presence of components on the magnetic layer side surface of the magnetic tape is also included within the scope of the magnetic layer side portion.
[0050] Examples of fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, behenic acid, erucic acid, and transoleic acid, with stearic acid, myristic acid, and palmitic acid being preferred, and stearic acid being more preferred. The fatty acids may be contained in the magnetic layer in the form of salts such as metal salts. Examples of fatty acid esters include esters of the various fatty acids described above. Specific examples include butyl myristate, butyl palmitate, butyl stearate, neopentyl glycol dioleate, sorbitol monostearate, sorbitol distearate, sorbitol tristearate, oleyl alcohol ester, isocetyl stearate, isothiyl stearate, octyl stearate, isooctyl stearate, pentyl stearate, and butoxyethyl stearate. Examples of fatty acid amides include the various fatty acid amides described above. Specific examples include lauryl amide, myristyl amide, palmitamide, stearyl amide, etc. Regarding fatty acids and fatty acid derivatives (amides, esters, etc.), the fatty acid derived from the fatty acid derivative preferably has the same or similar structure as the fatty acid used in combination. For example, when stearic acid is used as a fatty acid, it is preferable to use stearamide and / or stearate ester in combination.
[0051] In one embodiment, a magnetic tape containing one or more components selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides can be manufactured by forming a magnetic layer using a magnetic layer forming composition containing one or more of the aforementioned components. Furthermore, in another embodiment, a magnetic tape containing one or more of the aforementioned components in the magnetic layer side portion can be manufactured by forming a non-magnetic layer using a non-magnetic layer forming composition containing one or more of the aforementioned components. Also, in another embodiment, a magnetic tape containing one or more of the aforementioned components in the magnetic layer side portion can be manufactured by forming a non-magnetic layer using a non-magnetic layer forming composition containing one or more of the aforementioned components and forming a magnetic layer using a magnetic layer forming composition containing one or more of the aforementioned components. The non-magnetic layer can retain components such as fatty acids, fatty acid esters, and fatty acid amides that function as lubricants and supply them to the magnetic layer. The fatty acids, fatty acid esters, and fatty acid amides contained in the non-magnetic layer can be transferred to the magnetic layer and exist within the magnetic layer.
[0052] Regarding the fatty acid content, the fatty acid content of the composition for forming the magnetic layer is preferably 0.5 to 3.0 parts by weight relative to 100.0 parts by weight of the strong magnetic powder.
[0053] Regarding the fatty acid ester content, the fatty acid ester content of the composition for forming the magnetic layer is, for example, 0 to 10.0 parts by weight per 100.0 parts by weight of the strongly magnetic powder, preferably 1.0 to 7.0 parts by weight.
[0054] The fatty acid amide content of the composition for forming the magnetic layer is, for example, 0 to 1.0 parts by weight per 100.0 parts by weight of the strong magnetic powder, preferably 0.1 to 1.0 parts by weight.
[0055] The fatty acid content of the composition for forming the nonmagnetic layer is preferably 0.5 to 3.0 parts by weight relative to 100.0 parts by weight of the nonmagnetic powder. The fatty acid ester content of the composition for forming the nonmagnetic layer is, for example, 0 to 10.0 parts by weight relative to 100.0 parts by weight of the nonmagnetic powder, preferably 0 to 7.0 parts by weight. The fatty acid amide content of the composition for forming the nonmagnetic layer is, for example, 0 to 1.0 parts by weight per 100.0 parts by weight of the nonmagnetic powder, preferably 0.1 to 1.0 parts by weight.
[0056] Fluorine compounds In one embodiment, the magnetic tape may contain one or more fluorine compounds in the magnetic layer portion. As the fluorine compound, one commercially available compound or a compound synthesized by a known method may be used, or two or more may be mixed in any proportion. Fluorine atoms may be contained in the fluorine compound in various forms, such as fluorine-containing substituents like -CF3, -CHF2, and -CH2F. Furthermore, as the fluorine compound, it is preferable to have reactive groups capable of forming a crosslinking structure (hereinafter referred to as "crosslinking groups"). Examples of crosslinking groups include epoxy groups and isocyanate groups. Other crosslinking groups described later may also be mentioned. For example, it is conceivable that by directly forming a crosslinking structure between the crosslinking group of such a fluorine compound and other components (e.g., adhesives) contained in the magnetic layer, an anchoring effect of the fluorine compound can be obtained.
[0057] As a specific example of a fluorinated compound, a fluorinated polystyrene derivative containing a crosslinking group can be cited: it contains 1% by mass and 99% by mass of the repeating unit represented by the following formula [1], and contains 1% by mass and 95% by mass of repeating units containing a crosslinking group. This fluorinated polystyrene derivative containing a crosslinking group can be contained in the above-mentioned magnetic tape in the form of a crosslinked body formed by crosslinking reaction of at least a portion of the crosslinking group.
[0058] [Chemical Formula 1]
[0059] In formula [1], Y represents an alkyl group with 6 or fewer hydrogen atoms or carbon atoms, Q represents a divalent group containing at least one ether bond and a total number of 5 or fewer carbon atoms, and Rf0 represents a monovalent perfluoroether group containing at least one ether group and a total number of 25 or fewer carbon atoms, which may contain one hydrogen atom. z is an integer in the range of 1 to 3. The bonding position of Q on the aromatic nucleus can be any one of the ortho, meta, or para positions relative to the bonding position between the aromatic nucleus and the polymer backbone. Some or all of the hydrogen atoms bonded to the aromatic nucleus in formula [1] can be replaced by fluorine atoms.
[0060] The following is a more detailed explanation of equation [1].
[0061] In formula [1], Y is a hydrogen atom or an alkyl group having 6 or fewer carbon atoms. The alkyl group having 6 or fewer carbon atoms can be any one of a straight-chain alkyl group or a branched alkyl group. Specifically, examples include methyl, ethyl, normal-propyl, isopropyl, n-butyl, tertiary-butyl, isobutyl, secondary-butyl, n-pentyl, n-hexyl, etc. As Y, it is preferably an alkyl group having 4 or fewer carbon atoms, and more preferably a hydrogen atom and a methyl group.
[0062] In formula [1], Q is a divalent group containing at least one ether bond and having a total number of five or less carbon atoms. For example, the divalent group represented by the following formula [2] can be cited.
[0063] [Chemical Formula 2]
[0064] In Equation [2], a is 0 or 1, and b is an integer in the range of 0 or 1 to 3. The bond on the right side of Equation [2] is the bond bonded to Rf0.
[0065] For example, as Q, we can cite -O-, -OCH2-, -OCH2CH2-, -OCH2CH2CH2-, -OCH2CH2CH2CH2-, -OCH(CH3)CH2-, -OCH2CH(CH3)-, -OCH2CH(OH)CH2-, -OCH2CH(OH)CH2OCH2-, -CH2O-, -CH2OCH2-, -CH2OCH2CH2CH2-, -CH2OCH2CH2CH2CH2-, -CH2OCH2CH(CH3)OCH2-, -OCH2CH2OCH2-, -OCH2CH2OCH2CH2-, -CH2OCH2CH2OCH2-, -CH2OCH2CH2OCH2CH2-, etc. (the bonds on the right side of each group are bonds to Rf0).
[0066] In the above, from the viewpoint of easy polymer synthesis, -O-, -OCH2-, -OCH2CH2-, -CH2OCH2- and -CH2OCH2CH2- are preferred, and -O-, -OCH2- and -CH2OCH2- are more preferred. From the viewpoint of particularly excellent chemical stability, -O- is especially preferred.
[0067] In formula [1], Rf0 is a monovalent perfluoroether group containing at least one ether bond and may contain one hydrogen atom, and the total number of carbon atoms in Rf0 is 25 or less. The ratio of [total number of carbon atoms / number of ether bonds] in Rf0 is generally 2.0 or more and 9.0 or less, preferably 2.2 or more and 8.0 or less, more preferably 3.3 or more and 6.0 or less, and particularly preferably 3.5 or more and 5.0 or less.
[0068] As an example of Rf0, one can cite the group represented by the following formula [3].
[0069] [Chemical Formula 3]
[0070] In formula [3], Rf1 is a perfluoroalkyl group with 7 or fewer carbon atoms, Rf2 is one or more perfluoroalkyl groups selected from straight-chain or branched perfluoroalkyl groups with 4 or fewer carbon atoms, Rf3 is a perfluoroalkyl group with 3 or fewer carbon atoms or a perfluoroalkyl group with 3 or fewer carbon atoms in which one fluorine atom is replaced by a hydrogen atom, and L is an integer in the range of 0 or 1 to 10.
[0071] Examples of Rf1 include straight-chain or branched perfluoroalkyl groups with 7 or fewer carbon atoms, preferably perfluoroalkyl groups with 6 or fewer carbon atoms, and more preferably perfluoroalkyl groups with 3 or fewer carbon atoms.
[0072] Specific examples of Rf1 include CF3-, CF3CF2-, CF3CF2CF2-, (CF3)2CF-, CF3CF2CF2CF2-, CF3CF2CF2CF2CF2-, CF3CF2CF2CF2CF2CF2-, and CF3CF2CF2CF2CF2CF2CF2-. Among these, CF3CF2CF2-, CF3CF2CF2CF2-, and CF3CF2CF2CF2CF2CF2- are preferred, and CF3CF2CF2- is particularly preferred from the viewpoint of ease of synthesis.
[0073] Rf2 is one or more perfluoroalkyl groups selected from straight-chain or branched perfluoroalkyl groups having 4 or fewer carbon atoms. The number of carbon atoms in Rf2 is usually in the range of 1 to 4, preferably in the range of 1 to 3, and particularly preferably 3.
[0074] Specific examples of Rf2 include -CF(CF3)CF2-, -CF(CF3)-, -CF2-, -CF2CF2-, -CF2CF2CF2-, -CF2CF2CF2CF2-, and -CF2CF(CF3)CF2-. Among these, -CF(CF3)CF2-, -CF2-, -CF2CF2-, and -CF2CF2CF2- are preferred, and from the viewpoint of ease of synthesis, -CF(CF3)CF2- and -CF2CF2CF2- are particularly preferred. The bonds on the right side of each group in the specific examples of Rf2 are bonds that are bonded to oxygen atoms in the (Rf2O) unit in formula [3].
[0075] In formula [3], L is an integer in the range of 0 or 1 to 10, preferably an integer in the range of 0 or 1 to 6, more preferably an integer in the range of 0 or 1 to 3, even more preferably an integer in the range of 0 or 1 to 2, and especially preferably 0 or 1.
[0076] In equation [3] (Rf2O) LIn a partition, when Rf2 is composed of multiple perfluoroalkyl groups, different types of Rf2 can be randomly mixed and arranged, such as -CF(CF3)CF2O-CF2CF2CF2O-CF(CF3)CF2O-…, or multiple types of the same type of Rf2 can be arranged.
[0077] (Rf2O) is formed when Rf2 is composed of various perfluoroalkyl groups. L For example, the group represented by the following formula [4] can be cited.
[0078] -[CF(CF3)CF2O] n1 -[CF2CF2CF2O] n2 -[CF2CF2O] n3 -[CF2O] n4 [4]
[0079] In equation [4], n1, n2, n3 and n4 are each an independent integer in the range of 0 or 1 to 6. The sum of n1, n2, n3 and n4 (n1+n2+n3+n4) is the same as L in equation [3].
[0080] Rf3 is a perfluoroalkylene group with 3 or fewer carbon atoms, or a polyfluoroalkylene group with 1 fluorine atom replaced by a hydrogen atom.
[0081] Specific examples of Rf3 include -CF2-, -CF2CF2-, -CF(CF3)-, -CF2CF2CF2-, -CF(CF3)CF2-, -CF2CF(CF3)-, -CHFCF2-, and -CF2CHFCF2-. Among these, -CF2CF2-, -CF(CF3)-, and -CHFCF2- are preferred, and -CHFCF2- is particularly preferred from the viewpoint of ease of synthesis. The bonds on the right side of each group in the specific examples of Rf3 are bonds to Q.
[0082] Specific examples of Rf0 include the group represented by formula [R-1], the group represented by formula [R-2], the group represented by formula [R-3], and the group represented by formula [R-4].
[0083] [Chemical Formula 4]
[0084] [Chemical Formula 5]
[0085] [Chemical Formula 6]
[0086] [Chemical Formula 7]
[0087] Specific examples of the group represented by formula [R-1] include CF3CF2CF2OCHFCF2-, CF3CF2CF2OCF(CF3)CF2OCHFCF2-, CF3CF2CF2OCF(CF3)CF2OCF(CF3)CF2OCHFCF2- and CF3CF2CF2OCF(CF3)CF2OCF(CF3)CF2OCF(CF3)CF2OCHFCF2-.
[0088] Furthermore, as specific examples of the groups represented by formula [R-2], formula [R-3] or formula [R-4], examples can be given of groups in which the terminal CHFCF2 group of each structure is replaced by a CF(CF3) group, a CF2CF2 group or a CF2CHFCF2 group, respectively, in the specific examples of the groups represented by formula [R-1] above.
[0089] Furthermore, Rf0 can be a structure in which the terminal CF3CF2CF2 group in each of the groups of formula [R-1], formula [R-2], formula [R-3] or formula [R-4] is replaced with a straight-chain or branched perfluoroalkyl group having 1 to 7 carbon atoms, preferably 1 to 6. Examples of such perfluoroalkyl groups include CF3-, CF3CF2-, (CF3)2CF-, CF3CF2CF2CF2-, CF3CF2CF2CF2CF2-, and CF3CF2CF2CF2CF2CF2-.
[0090] In Equation [1], z is an integer in the range of 1 to 3. From the point of view that it is easy to synthesize, it is more preferable to have z as 1.
[0091] In formula [1], the bonding position of Q on the aromatic core can be any one of the ortho, meta or para positions relative to the bonding position between the aromatic core and the polymer backbone. From the point of view of easy synthesis and easy availability of raw materials, the para position is preferred.
[0092] Some or all of the hydrogen atoms bonded to the aromatic nucleus in formula [1] may be replaced by fluorine atoms. From the point of view of easy synthesis, the structure that is not replaced by fluorine atoms is preferred.
[0093] As the repeating unit represented by formula [1], it is preferably the repeating unit represented by formula [1-1] below, and more preferably the repeating unit represented by formula [1-2] below.
[0094] [Chemical Formula 8]
[0095] In formula [1-1], Y1 represents a hydrogen atom or a methyl group, and Q1 represents a divalent group containing an ether bond with 3 or fewer carbon atoms. Rf 01 Rfa1-O-[CF(CF3)CF2O] m1 -[CF2CF2CF2O] m2 -[CF2CF2O] m3 -[CF2O] m4 -Rfc1-, Rfa1 is a perfluoroalkyl group with 1 to 6 carbon atoms, m1, m2, m3 and m4 are each independently an integer in the range of 0 or 1 to 6, the sum of m1, m2, m3 and m4 (m1+m2+m3+m4) is an integer in the range of 0 or 1 to 6, and Rfc1 represents a perfluoroalkylene group with 3 or fewer carbon atoms that may contain 1 hydrogen atom.
[0096] The following is a more detailed explanation of equation [1-1].
[0097] Q1 is a divalent group containing an ether bond with 3 or fewer carbon atoms. Specific examples include -O-, -OCH2-, -CH2O-, -OCH2CH2-, -CH2OCH2-, and -CH2OCH2CH2-. Q1 is more preferably -O-, -CH2OCH2-, or -OCH2-, and especially preferably -O-. The bonding on the right side of each group in the specific examples of Q1 is with Rf in formula [1-1]. 01 Bonded bonds.
[0098] The sum of m1, m2, m3, and m4 (m1+m2+m3+m4) is an integer ranging from 0 to 6, preferably from 0 to 3, more preferably from 0 to 2, and especially preferably from 0 to 1. Rfc1 is a perfluoroalkylene group containing 3 or fewer carbon atoms and may contain 1 hydrogen atom. Specific examples include -CF2CF2-, -CF(CF3)-, -CF2-, -CF2CHFCF2-, and -CHFCF2-. As Rfc1, -CF(CF3)- and -CHFCF2- are more preferred, and -CHFCF2- is especially preferred. The bond on the right side of each group in the specific examples of Rfc1 is a bond bonded to Q1 in formula [1-1].
[0099] In formula [1-1], the bonding position of Q1 on the aromatic core can be any one of the ortho, meta, or para positions relative to the bonding position between the aromatic core and the polymer backbone. From the viewpoint of easy synthesis and easy availability of raw materials, the para position is preferred.
[0100] [Chemical Formula 9]
[0101] In formula [1-2], Y2 represents a hydrogen atom or a methyl group, L1 is an integer in the range of 0 or 1 to 6, and Rfa2 represents a perfluoroalkyl group with 1 to 6 carbon atoms.
[0102] L1 is an integer in the range of 0 or 1 to 6, preferably 0 to 4, more preferably 0 to 2, and especially preferably 0 or 1. Furthermore, Rfa2 is a perfluoroalkyl group having 1 to 6 carbon atoms, preferably a perfluoroalkyl group having 2 to 4 carbon atoms, and especially preferably CF3CF2CF2-.
[0103] Fluorinated polystyrene derivatives containing repeating units represented by formula [1], formula [1-1], or formula [1-2] can be manufactured by reacting a polystyrene derivative containing reactive groups, such as a polymer containing repeating units of the p-hydroxystyrene type or a polymer containing repeating units derived from p-chloromethylstyrene, with a perfluoro(poly)ether compound or a polyfluoro(poly)ether compound containing active end groups. For example, it can be manufactured by reacting a polymer containing repeating units of the p-hydroxystyrene type with CF2=CF-[OCF2CF(CF3)]. L1 Polystyrene derivatives containing repeating units of formula [1-2] are produced by the addition reaction of -ORfa2 type monomers (L1 and Rfa2 are the same as in formula [1-2]). Furthermore, polystyrene derivatives containing repeating units of formula [1-2] are produced through the addition reaction of monomers of the -ORfa2 type (L1 and Rfa2 are the same as in formula [1-2]). Z The copolymerization of monomers with the same structure (Y, Q, Rf0 and z as in formula [1], Ph is an abbreviation for phenylene) can also produce fluorinated polystyrene derivatives containing repeating units represented by formula [1].
[0104] The content of the repeating unit represented by formula [1] (preferably formula [1-1], more preferably formula [1-2]) in the above-mentioned fluorinated polystyrene derivative containing crosslinking groups is 1% by mass or more and 99% by mass or less. The lower limit of the content of the repeating unit represented by formula [1] in the above-mentioned fluorinated polystyrene derivative containing crosslinking groups is 1% by mass or more, and may also be 5% by mass or more, 10% by mass or more, 30% by mass or more, or 50% by mass or more. Furthermore, the upper limit of the content of the repeating unit is 99% by mass or less, and may also be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0105] In addition to the repeating unit represented by formula [1], the aforementioned fluorinated polystyrene derivative containing crosslinking groups also includes repeating units containing crosslinking groups in the range of 1% to 95% by mass or more. As a repeating unit containing crosslinking groups in the aforementioned fluorinated polystyrene derivative containing crosslinking groups, for example, it is preferably a repeating unit containing at least one type of crosslinking group selected from active hydrogen-containing groups, carbon-carbon multiple bond-containing groups, epoxy groups, isocyanate groups, and alkoxysilane groups. Examples of active hydrogen-containing groups include hydroxyl (phenolic hydroxyl, alcoholic hydroxyl), amino, thiol, carboxyl, etc. Examples of carbon-carbon multiple bond-containing groups include acrylate groups, methacrylate groups, styrene groups, allyl, ethyleneoxy, trifluoroethyleneoxy (CF2=CFO-), maleimide groups, etc., or propargyl, ethynyl, etc., carbon-carbon triple bond-containing groups. As an epoxy group, for example, a glycidyl group linked to various groups can be cited. Examples of isocyanate groups include aliphatic isocyanate groups and aromatic isocyanate groups. Examples of alkoxysilyl groups include trialkoxysilyl, dialkoxymonosilyl, and monoalkoxydialkylsilyl.
[0106] The crosslinking groups in the repeating units containing crosslinking groups described above can undergo crosslinking reactions in various ways. For example, the following crosslinking reactions can be cited.
[0107] (i) Crosslinking through the reaction of active hydrogen type crosslinking groups with multifunctional substances (e.g., crosslinking through the reaction of active hydrogen (alcohols, phenols, amines, thiols, carboxylic acids, etc.) type crosslinking groups with multifunctional compounds (polyisocyanates, polyepoxides, etc.)
[0108] (ii) Crosslinking through the reaction of highly active crosslinking groups with multifunctional substances (e.g., crosslinking through the reaction of isocyanate-type or epoxy-type crosslinking groups with multivalent active hydrogen compounds (polyols, polyphenols, polyamines, polythiols, polycarboxylic acid compounds)).
[0109] (iii) Crosslinking types resulting from polymerization of a single type of crosslinking group (e.g., (meth)acrylate crosslinking groups, styrene crosslinking groups, epoxy crosslinking groups, oxetane crosslinking groups, cyclic sulfur crosslinking groups, etc. Examples of polymerization methods: free radical polymerization, cationic polymerization, anionic polymerization, thermal polymerization, and ultraviolet irradiation.)
[0110] The above-mentioned (meth)acrylates include acrylates and methacrylates.
[0111] (iV) A type of crosslinking formed by the connection of several single-type crosslinking groups (e.g., ethynyl or propargyl crosslinking groups, alkoxysilane crosslinking groups, trifluoroethyleneoxy crosslinking groups, etc.).
[0112] The following are specific examples of repeating units containing crosslinking groups in the aforementioned fluorinated polystyrene derivatives containing crosslinking groups. However, the repeating units containing crosslinking groups in the aforementioned fluorinated polystyrene derivatives containing crosslinking groups are not limited to these examples.
[0113] [Chemical Formula 10]
[0114] [Chemical Formula 11]
[0115] [Chemical Formula 12]
[0116] [Chemical Formula 13]
[0117] [Chemical Formula 14]
[0118] [Chemical Formula 15]
[0119] The repeating units containing cross-linked groups in the aforementioned fluorinated polystyrene derivatives can be introduced by various methods.
[0120] For example, polymers containing p-hydroxystyrene units as repeating units can be manufactured through hydrolysis or other processes involving polymers containing repeating units derived from p-acetoxystyrene. The p-hydroxystyrene unit can be used as a phenolic, active hydrogen-type crosslinking group. Furthermore, the aforementioned p-hydroxystyrene unit can be readily converted into various repeating units containing crosslinking groups due to its high reactivity. For example, the -OH group of the p-hydroxystyrene unit can be converted into various types of crosslinking groups. Similarly, the aliphatic alcohol groups of copolymers containing repeating units such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate can also be converted into various types of crosslinking groups.
[0121] [Chemical Formula 16]
[0122] The repeating units containing crosslinking groups in the aforementioned fluorinated polystyrene derivatives can also be introduced by copolymerization of vinyl polymerizable monomers containing various crosslinking groups with polystyrene derivative monomers that form repeating units represented by formula [1] (preferably formula [1-1], more preferably formula [1-2]). Examples of vinyl polymerizable (free radical polymerizable, cationic polymerizable, or anionic polymerizable) monomers in which such crosslinking groups can be introduced are shown below. However, vinyl polymerizable monomers containing various crosslinking groups are not limited to these. Furthermore, it is also possible to copolymerize vinyl polymerizable monomers after stabilizing active groups such as active hydrogen groups and isocyanate groups with protecting groups, and then activate them by removing the protecting groups.
[0123] [Chemical Formula 17]
[0124] [Chemical Formula 18]
[0125] [Chemical Formula 19]
[0126] [Chemical Formula 20]
[0127] [Chemical Formula 21]
[0128] The content of the repeating unit containing the crosslinking group in the above-mentioned fluorinated polystyrene derivative containing the crosslinking group is 1% by mass or more and 95% by mass or less. The content of the repeating unit containing the crosslinking group in the above-mentioned fluorinated polystyrene derivative containing the crosslinking group is preferably selected from the range of 1% by mass or more and 80% by mass or less, 1% by mass or more and 60% by mass or less, or 1% by mass or more and 50% by mass or less. The repeating unit containing the crosslinking group in the above-mentioned fluorinated polystyrene derivative containing the crosslinking group can be one type or multiple types.
[0129] In the above-mentioned fluorinated polystyrene derivatives containing crosslinking groups, in addition to the repeating units represented by formula [1], formula [1-1] or formula [1-2] and the repeating units containing crosslinking groups, one or more repeating units of various structures may be included to adjust the properties of the crosslinked body formed by crosslinking at least a portion of the crosslinking groups of the above-mentioned fluorinated polystyrene derivatives containing crosslinking groups.
[0130] For example, in the above-mentioned fluorinated polystyrene derivatives containing crosslinking groups, the repeating units other than those represented by formula [1], formula [1-1] or formula [1-2] and repeating units containing crosslinking groups may include one or more monomer units of free radical polymerizability, cationic polymerizability or anionic polymerizability. Specific examples of polymerizable monomers include, for example, various substituted styrene, unsubstituted styrene, vinylnaphthalene, acenaphthene, maleic anhydride or its derivatives, maleimide derivatives, (meth)acrylonitrile, (meth)acrylamide and its derivatives, various (meth)acrylates, fluorinated (meth)acrylates, various fluorinated olefins, various vinyl carboxylic acids or various vinyl ethers, and other polymerizable monomers.
[0131] In the above-mentioned fluorinated polystyrene derivatives containing crosslinking groups, the content of repeating units represented by formula [1], formula [1-1] or formula [1-2] and other repeating units other than repeating units containing crosslinking groups may be in the range of 0% or more and 90% or less, 0% or more and 60% or less, or 0% or more and 40% or less, relative to the total mass of the fluorinated polystyrene derivatives containing crosslinking groups.
[0132] As a method for manufacturing a polystyrene derivative containing a cross-linked group, which includes repeating units other than the repeating units represented by the above formula [1] and repeating units containing a cross-linked group, the following methods can be exemplified, for example. However, it is not limited to these methods. (1) By CF2=CF-[OCF2CF(CF3)] L1 A method for manufacturing perfluoro(poly)ether compounds with active end groups, such as ORfa2 (L1, Rfa2 and the same as in formulas [1-2]), by adding phenolic hydroxyl groups to copolymers formed from p-hydroxystyrene units, repeating units containing crosslinking groups, and various monomer units. (2) Using CH2=CY-Ph-[Q-Rf o ] Z The structural monomers (Y, Q, Rf) o And z is the same as in formula [1], Ph is the abbreviation for phenylene), a method for manufacturing copolymers of monomers containing crosslinking groups and various monomers.
[0133] As the aforementioned fluorinated polystyrene derivative containing crosslinking groups, polymers with various structures and sequences manufactured by various manufacturing methods can be used. For example, the aforementioned fluorinated polystyrene derivative containing crosslinking groups can be manufactured by various copolymerization methods such as free radical copolymerization, cationic copolymerization, or anionic copolymerization. Furthermore, polymers with desired crosslinking reactivity can be manufactured by converting the reactive groups contained in the copolymers manufactured by such copolymerization into other types of reactive groups. Moreover, as the aforementioned fluorinated polystyrene derivative containing crosslinking groups, polymers with various structures such as random copolymers, block copolymers, graft copolymers, or star polymers can be used.
[0134] To manufacture the aforementioned magnetic tape, one or more fluorine-based compounds can be used. In one method, by adding a fluorine-based compound as a component of the magnetic layer forming composition (so-called magnetic layer infill), a magnetic tape containing a fluorine-based compound in the magnetic layer side portion can be manufactured. "Infill" is an abbreviation for internal addition. Furthermore, in another method, the fluorine-based compound can be present in the magnetic layer side portion by preparing a coating liquid containing a fluorine-based compound and applying the coating liquid to the surface of the magnetic layer (so-called outer coating). The amount of fluorine-based compound added to the magnetic layer forming composition relative to 100.0 parts by weight of strong magnetic powder can, for example, be 0.3 parts by weight or more and 3.0 parts by weight or less, 0.3 parts by weight or more and 2.0 parts by weight or less, or 0.5 parts by weight or more and 1.5 parts by weight or less. However, these ranges are examples, and the amount added can be adjusted according to the type of fluorine-based compound, etc.
[0135] The magnetic layer described above can be directly applied to the surface of a non-magnetic support, or it can be applied indirectly via a non-magnetic layer.
[0136] <Non-magnetic layer> The magnetic tape described above can have a magnetic layer directly on the surface of a non-magnetic support, or it can have a non-magnetic layer containing non-magnetic powder between the non-magnetic support and the magnetic layer. The non-magnetic powder contained in the non-magnetic layer can be inorganic or organic powder. Furthermore, carbon black and the like can also be used. Examples of inorganic powders include powders of metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, and metal sulfides. These non-magnetic powders can be obtained as commercially available products or manufactured using known methods. For details, please refer to paragraphs 0036 to 0039 of Japanese Patent Application Publication No. 2010-24113. The content (filling rate) of the non-magnetic powder in the non-magnetic layer is preferably in the range of 50 to 90% by mass relative to the total mass of the non-magnetic layer, and more preferably in the range of 60 to 90% by mass.
[0137] The non-magnetic layer contains non-magnetic powder and may also contain a binder along with the non-magnetic powder. Details regarding the binder, additives, and other substances in the non-magnetic layer can be found in known techniques related to non-magnetic layers. Furthermore, for example, known techniques related to magnetic layers can be applied regarding the type and content of the binder, and the type and content of the additives.
[0138] The non-magnetic layer of the aforementioned magnetic tape also includes a substantially non-magnetic layer that, along with the non-magnetic powder, contains, for example, as an impurity or intentionally in the form of a small amount of strongly magnetic powder. Here, a substantially non-magnetic layer refers to a layer with a remanent magnetic flux density of 10 mT or less and a coercivity of 7.96 kA / m (100 Oe) or less, or a remanent magnetic flux density of 10 mT or less and a coercivity of 7.96 kA / m (100 Oe) or less. Preferably, the non-magnetic layer does not have remanent magnetic flux density or magnetic retention force.
[0139] <Back Coating> The magnetic tape described above may also have a back coating containing non-magnetic powder on the surface of the non-magnetic support opposite to the surface with the magnetic layer. Alternatively, the magnetic tape may be a magnetic tape without a back coating. The back coating may contain one or both of carbon black and inorganic powder.
[0140] The back coating contains non-magnetic powder and may include a binder or more additives. Regarding the binder and additives in the back coating, prior art related to the back coating itself, as well as prior art related to the formulation of the magnetic and / or non-magnetic layers, may be applied. For example, regarding the back coating, reference can be made to paragraphs 0018 to 0020 of Japanese Patent Application Publication No. 2006-331625 and lines 65-38 of column 4 of U.S. Patent No. 7,029,774.
[0141] <Non-magnetic support> Next, the non-magnetic support will be described. Examples of non-magnetic supports (hereinafter simply referred to as "supports") include known supports such as polyethylene terephthalate (PET), polyethylene naphthalate (PAN), and other polyesters subjected to biaxial stretching, polyamides such as aromatic polyamides, and polyamide-imide. Among these, PET, PAN, and polyamides are preferred. These supports can be pre-treated with corona discharge, plasma treatment, easy-bonding treatment, heat treatment, etc.
[0142] In one embodiment, the support contained in the magnetic tape may be a polyester support. In this invention and specification, "polyester" refers to a resin containing multiple ester bonds. "Polyester support" refers to a support containing at least one layer of polyester film. "Polyester film" refers to a film in which polyester is the most abundant component by mass in the composition of the film. In this invention and specification, "polyester support" includes supports in which all resin films contained are polyester films and supports containing polyester films and other resin films. Specific examples of polyester supports include single-layer polyester films, laminated films of two or more polyester films with the same composition, laminated films of two or more polyester films with different compositions, and laminated films containing one or more polyester films and one or more resin films other than polyester. An adhesive layer may also be arbitrarily included between adjacent layers in the laminated film. Furthermore, the polyester support may arbitrarily contain a metal film and / or a metal oxide film formed on one or both surfaces by vapor deposition or the like. The same applies to the "aromatic polyester support", "polyethylene terephthalate support" and "polyethylene naphthalate support" in this invention and specification.
[0143] The polyester support can be an aromatic polyester support. In this invention and this specification, "aromatic polyester" refers to a resin containing an aromatic backbone and multiple ester bonds, and "aromatic polyester support" refers to a support containing at least one layer of aromatic polyester film.
[0144] There are no particular limitations on the aromatic rings contained in the aromatic skeleton of aromatic polyesters. Specific examples of aromatic rings include benzene rings and naphthalene rings. For example, polyethylene terephthalate (PET) is a polyester containing benzene rings and is a resin obtained by polycondensation of ethylene glycol with terephthalic acid and / or dimethyl terephthalate. The term "polyethylene terephthalate" in this invention and specification also includes compounds having a structure containing one or more other components (e.g., copolymer components, components introduced into the ends or side chains, etc.) in addition to the components described above. Polyethylene naphthalate (PEN) is a polyester containing a naphthalene ring, and is a resin obtained by esterification of dimethyl 2,6-naphthalate with ethylene glycol followed by transesterification and polycondensation. The term "polyethylene naphthalate" in this invention and specification also includes compounds having a structure containing one or more other components (e.g., copolymer components, components introduced into the ends or side chains, etc.) in addition to the components described above.
[0145] <Various Thicknesses> The total thickness of the magnetic tape is preferably 5.6 μm or less, more preferably 5.5 μm or less, even more preferably 5.4 μm or less, even more preferably 5.3 μm or less, even more preferably 5.2 μm or less, even more preferably 5.0 μm or less, and still more preferably 4.8 μm or less. With the tremendous increase in information volume in recent years, there is a demand for higher recording capacity (high capacity) of magnetic tapes. For example, regarding magnetic tapes (i.e., magnetic tapes), methods for achieving high capacity include: reducing the thickness of the magnetic tape and increasing the length of the magnetic tape contained in each tape reel. Furthermore, from the viewpoint of ease of operation, the total thickness of the magnetic tape is preferably 3.0 μm or more, more preferably 3.5 μm or more, and even more preferably 4.0 μm or more.
[0146] For example, the total thickness of a magnetic tape can be determined by the following methods. Ten samples (e.g., 5–10 cm in length) are cut from any portion of the magnetic tape and overlapped to measure the thickness. The total thickness is obtained by dividing the measured thickness by 10 (the thickness of each sample). This thickness measurement can be performed using a known measuring instrument capable of measuring thickness on the order of 0.1 μm.
[0147] The thickness of the non-magnetic support is preferably 3.0 to 5.0 μm. The thickness of the magnetic layer can be optimized based on factors such as the saturation magnetization of the magnetic head, the head gap length, and the frequency band of the recorded signal. It is typically 0.01 μm to 0.15 μm, and from the viewpoint of high-density recording, 0.02 μm to 0.12 μm is preferred, and 0.03 μm to 0.1 μm is even more preferred. At least one magnetic layer is required; the magnetic layer can be divided into two or more magnetic layers with different magnetic properties, and known structures related to multilayer magnetic layers can be applied. When divided into two or more magnetic layers, the thickness of the magnetic layer refers to the total thickness of these layers. The thickness of the non-magnetic layer is, for example, 0.1 to 1.5 μm, preferably 0.1 to 1.0 μm, and more preferably 0.1 to 0.7 μm. The thickness of the back coating is preferably less than 0.9 μm, and more preferably 0.1 to 0.7 μm. The thickness of the magnetic layer and other thicknesses can be determined using the following methods. After exposing a cross-section of the magnetic tape along its thickness direction using an ion beam, cross-sectional observation is performed on the exposed section using a scanning electron microscope or a transmission electron microscope. Various thicknesses can be calculated as the arithmetic mean of the thicknesses obtained from any two locations in the cross-sectional observation. Alternatively, various thicknesses can also be calculated as design thicknesses based on manufacturing conditions, etc.
[0148] <Manufacturing Process> The compositions used to form the magnetic layer, non-magnetic layer, and back coating typically contain a solvent, as well as the various components described above. One or more organic solvents commonly used in the manufacture of coated magnetic recording media can be used as the solvent. Specifically, the composition can be used in any ratio with ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, isophorone, and tetrahydrofuran; alcohol solvents such as methanol, ethanol, propanol, butanol, isobutanol, isopropanol, and methylcyclohexanol; ester solvents such as methyl acetate, butyl acetate, isobutyl acetate, isopropyl acetate, ethyl lactate, and ethylene glycol monoacetate; ethylene glycol ether solvents such as ethylene glycol dimethyl ether, ethylene glycol monoethyl ether, and dioxane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, cresol, and chlorobenzene; chlorinated hydrocarbon solvents such as dichloromethane, dichloroethane, carbon tetrachloride, chloroform, chloroethanol, and dichlorobenzene; N,N-dimethylformamide; and hexane. From the viewpoint of the solubility of binders commonly used in coated magnetic recording media, it is preferable to include one or more ketone solvents in the magnetic layer forming composition. The amount of solvent in the composition for forming each layer is not particularly limited and can be the same as that in the composition for forming each layer of a conventional coated magnetic recording medium.
[0149] The process of preparing the composition for each layer formation typically includes at least a mixing process, a dispersion process, and a blending process set up before and after these processes as needed. Each process can be divided into two or more stages. Various components used in the preparation of the composition for each layer formation can be added at the beginning or in the middle of any process. Furthermore, the components can be added separately in two or more processes.
[0150] To prepare the composition for forming each layer, known techniques can be used. In the mixing process, kneaders with strong mixing power, such as open kneaders, continuous kneaders, pressure kneaders, and extruders, are preferred. Details of these mixing processes are described in Japanese Patent Application Publications Nos. 1-106338 and 1-79274. Furthermore, to disperse the composition for forming each layer, one or more types of dispersed beads selected from the group consisting of glass beads and other dispersed beads can be used as the dispersion medium. Zirconia beads, titanium dioxide beads, and steel beads, which are high-density dispersed beads, are preferred. The particle size (bead diameter) and filling rate of these dispersed beads can be optimized. Known dispersers can be used. The composition for forming each layer can be filtered by known methods before the coating process. Filtration can be performed, for example, by using a filter. For example, filters with a pore size of 0.01 to 3 μm (e.g., glass fiber filters, polypropylene filters, etc.) can be used as filters for filtration.
[0151] Regarding the preparation of the composition for forming the magnetic layer, the centrifugal separation for preparing the abrasive dispersion is as described above.
[0152] The magnetic layer can be formed by directly coating the magnetic layer forming composition onto a non-magnetic support, or by applying multiple layers of the magnetic layer forming composition sequentially or simultaneously. The back coating can be formed by coating the back coating forming composition onto the side of the non-magnetic support opposite to the side with the magnetic layer (or where an additional magnetic layer is provided). For details regarding the coatings used to form each layer, please refer to paragraph 0051 of Japanese Patent Application Publication No. 2010-24113.
[0153] After the coating process, various treatments can be performed, such as drying, magnetic layer orientation, and surface smoothing (calendering). For details of these processes, please refer to known technologies such as paragraphs 0052 to 0057 of Japanese Patent Application Publication No. 2010-24113.
[0154] For example, an orientation treatment can be performed on the coating layer of the magnetic layer forming composition while the coating layer is in an undried state. Regarding the orientation treatment, various known techniques, including those described in paragraph 0067 of Japanese Patent Application Publication No. 2010-231843, can be applied. For example, vertical orientation treatment can be performed using known methods such as the method of using opposite-pole magnets. In the orientation region, the drying speed of the coating layer can be controlled based on the temperature and flow rate of the drying air and / or the conveying speed of the non-magnetic support in the orientation region where the aforementioned coating layer is formed. Furthermore, the coating layer can be pre-dried before being conveyed to the orientation region. If the orientation conditions are enhanced, the rectangularity ratio of the magnetic tape tends to increase. The rectangularity ratio of the magnetic tape can be controlled based on the presence or absence of orientation treatment, the orientation conditions of the orientation treatment, etc. Examples of orientation conditions include the strength of the magnet used for the orientation treatment, the duration of magnetic field application, etc.
[0155] Furthermore, regarding the calendering process, strengthening the calendering conditions results in a smoother surface of the magnetic layer of the magnetic tape. Examples of calendering conditions include calendering pressure, calendering temperature (surface temperature of the calendering rolls), calendering speed, and the hardness of the calendering rolls. Increasing the values of calendering pressure, calendering temperature, and the hardness of the calendering rolls intensifies the calendering process, while slowing down the calendering speed further intensifies the calendering process. For example, the calendering pressure (linear pressure) can be 200–500 kN / m, preferably 250–350 kN / m. The calendering temperature (surface temperature of the calendering rolls) can be, for example, 85–120°C, preferably 90–110°C, and more preferably 95–110°C. The calendering speed can be, for example, 50–300 m / s, preferably 50–200 m / s.
[0156] <Vertical Rectangular Ratio> In one embodiment, the vertical rectangularity ratio of the magnetic tape can be 0.60 or higher, preferably 0.63 or higher, and more preferably 0.65 or higher. The maximum value of the vertical rectangularity ratio is, in principle, 1.00. Therefore, the vertical rectangularity ratio of the magnetic tape is 1.00 or lower, and can be 0.95 or lower, 0.90 or lower, 0.85 or lower, 0.80 or lower, 0.75 or lower, or 0.70 or lower. From the viewpoint of improving electromagnetic conversion characteristics, a larger value for the vertical rectangularity ratio is preferable.
[0157] In this invention and specification, the vertical rectangularity ratio of the magnetic tape is the rectangularity ratio measured in the vertical direction of the magnetic tape. The vertical direction refers to the direction orthogonal to the surface of the magnetic tape, and can also be called the thickness direction. The vertical rectangularity ratio is obtained from the vertical direction MH curve. The vertical rectangularity ratio is determined by scanning the external magnetic field applied to the magnetic tape within a magnetic field strength range of -1197 kA / m to 1197 kA / m using a vibrating specimen magnetometer. Regarding magnetic field strength, the conversion factor from Oe (Oersted) to SI units A / m is 10. 3 / 4π. The range of -1197kA / m to 1197kA / m has the same meaning as the range of -15kOe to 15kOe. In this invention and this specification, the measurements performed using a vibrating sample type magnetometer are conducted at a measurement temperature of 24℃ ± 1℃. Regarding the scanning of the external magnetic field, a measurement sample cut from the magnetic tape of the object being measured is used, and the scanning conditions shown in Table 2 below are followed, with the average number at each step size being 1. By scanning the external magnetic field in this way, a hysteresis curve (referred to as the "MH curve") is obtained in the range of magnetic field strength of -1197kA / m to 1197kA / m. The MH curve obtained by arranging the measurement sample in the vibrating sample type magnetometer in a manner orthogonal to the surface of the measurement sample in the direction of application of the external magnetic field is called the "vertical direction MH curve". The above-mentioned "orthogonality" includes the range of errors permissible in the technical field to which this invention pertains. The above-mentioned range of errors refers, for example, to a range of strictly orthogonal less than ±10°, preferably strictly orthogonal within ±5°, and more preferably within ±3°. The measured value is obtained by subtracting the background noise from the magnetization of the sample probe of the vibrating sample magnetometer. Furthermore, the rectangle ratio is the rectangle ratio without anti-magnetic field correction. Known devices such as those used in the embodiments described later can be used as the vibrating sample magnetometer (VSM). The sample used for measurement only needs to have a saturation magnetization of less than 5 × 10⁻⁶ based on the MH curve obtained in this way. -6 ~10×10 -6 A·m 2 (5×10) -3 ~10×10-3 The size and shape are not limited as long as saturation magnetization within that range can be achieved.
[0158] For example, magnetic tape is typically housed in a tape cassette, which is then mounted in a magnetic recording and playback device. In order to enable head tracking in the magnetic recording and playback device, a servo pattern can be formed on the magnetic tape using known methods. "Servo pattern formation" can also be referred to as "servo signal recording." The formation of a servo pattern will be explained below using magnetic tape as an example.
[0159] Servo patterns are typically formed along the length of the magnetic tape. Examples of control methods utilizing servo signals (servo control) include time-based servo (TBS), amplitude servo, and frequency servo.
[0160] As shown in ECMA (European Computer Manufacturers Association) 319 (June 2001), time-based servo technology is used in LTO (Linear Tape-Open) magnetic tapes (generally referred to as "LTO tapes"). In this time-based servo technology, the servo pattern is constructed by continuously arranging multiple pairs of non-parallel magnetic stripes (also called "servo stripes") along the length of the tape. As mentioned above, the servo pattern is constructed by a pair of non-parallel magnetic stripes to notify the servo signal readout element passing over the servo pattern of its position. Specifically, the pair of magnetic stripes is formed with their intervals continuously varying along the width of the tape. By reading this interval by the servo signal readout element, the relative position of the servo pattern and the servo signal readout element can be determined. This information of relative position enables data track tracking. Therefore, multiple servo tracks are typically arranged along the width of the tape on the servo pattern.
[0161] A servo band consists of continuous servo signals running along the length of the magnetic tape. Multiple servo bands are typically present on the tape. For example, in an LTO tape, there are five servo bands. The area between two adjacent servo bands is called the data band. The data band consists of multiple data tracks, each corresponding to a servo track.
[0162] Furthermore, in one approach, as shown in Japanese Patent Application Publication No. 2004-318983, information indicating the serial number of the servo band is embedded in each servo band (also referred to as "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information"). This servo band ID is recorded by offsetting specific servo stripes in a pair of servo stripes that exist multiple times within the servo band, by relative displacement of their positions along the length of the magnetic tape. Specifically, the offsetting method of specific servo stripes in a pair of servo stripes that exist multiple times is changed for each servo band. Therefore, the recorded servo band ID is unique for each servo band, and thus, by reading a single servo band using a servo signal reading element, the servo band can be uniquely identified.
[0163] Another method for uniquely identifying servo strips is the interleaving method, as shown in ECMA-319 (June 2001). In this interleaving method, multiple pairs of non-parallel magnetic stripes are arranged consecutively along the length of the magnetic tape and recorded in a manner that each servo strip is staggered along the length of the tape. The combination of this staggering method between adjacent servo strips is unique throughout the entire magnetic tape, thus allowing for unique identification of the servo strip when the servo pattern is read using two servo signal readout elements.
[0164] Furthermore, as shown in ECMA-319 (June 2001), information indicating the position along the length of the magnetic tape (also known as "LPOS (Longitudinal Position) information") is typically embedded in each servo tape. Similar to UDIM information, this LPOS information is recorded by offsetting the positions of a pair of servo stripes along the length of the tape. However, unlike UDIM information, the same signal is recorded in each servo tape in this LPOS information.
[0165] Other information, different from the UDIM and LPOS information mentioned above, can also be embedded into the server tape. In this case, the embedded information can vary for each server tape, like the UDIM information, or it can be universal across all server tapes, like the LPOS information. Furthermore, other methods besides those described above can also be used as a way to embed information in the servo stripes. For example, a specified code can be recorded by extracting a specified pair from a pair of servo stripe groups.
[0166] The magnetic head used for servo pattern formation is called a servo write head. A servo write head typically has a pair of gaps corresponding to the aforementioned pair of magnetic strips, and the number of these gaps is the same as the number of servo tapes. A core and a coil are usually connected to each pair of gaps. By supplying current pulses to the coils, the magnetic field generated in the core can produce a leakage magnetic field in the pair of gaps. During servo pattern formation, by feeding the magnetic tape onto the servo write head while simultaneously inputting current pulses, the magnetic pattern corresponding to the pair of gaps can be transferred onto the magnetic tape, thereby forming a servo pattern. The width of each gap can be appropriately set according to the density of the formed servo pattern. For example, the width of each gap can be set to less than 1 μm, 1–10 μm, or more than 10 μm.
[0167] Before forming servo patterns on the magnetic tape, the tape is typically demagnetized (erased). This erasure process can be performed by applying the same magnetic field to the tape using either a DC or AC magnet. There are two types of erasure: DC (Direct Current) erasure and AC (Alternating Current) erasure. AC erasure is performed by gradually reducing the strength of the magnetic field while reversing its direction. DC erasure, on the other hand, is performed by applying a directional magnetic field to the tape. DC erasure has two further methods. The first method is horizontal DC erasure, which applies a directional magnetic field along the length of the tape. The second method is vertical DC erasure, which applies a directional magnetic field along the thickness of the tape. Erasure can be performed on the entire tape or on each servo section of the tape.
[0168] The orientation of the magnetic field in the formed servo pattern depends on the erasure orientation. For example, when a horizontal DC erasure is applied to the magnetic tape, the servo pattern is formed with the magnetic field orientation opposite to the erasure orientation. This increases the output of the servo signal obtained by reading the servo pattern. As shown in Japanese Patent Application Publication No. 2012-53940, when a magnetic pattern using the aforementioned gap is transferred to a magnetic tape that has been vertically DC erased, the servo signal obtained by reading the formed servo pattern is a unipolar pulse shape. On the other hand, when a magnetic pattern using the aforementioned gap is transferred to a magnetic tape that has been horizontally DC erased, the servo signal obtained by reading the formed servo pattern is a bipolar pulse shape.
[0169] [Cassette Tape Case] One aspect of the present invention relates to a magnetic tape cassette comprising the aforementioned magnetic tape.
[0170] The details of the magnetic tapes included in the aforementioned tape cassette are as described above.
[0171] In a magnetic tape cassette, the magnetic tape is typically housed inside the cassette body while being wound onto a reel. The reel is configured to rotate within the cassette body. Single-reel cassettes with one reel inside the cassette body and double-reel cassettes with two reels inside the cassette body are widely used. When a single-reel cassette is installed in a magnetic recording and playback device for recording and / or reproducing data on the magnetic tape, the magnetic tape is pulled from the cassette and wound onto the reel on the magnetic recording and playback device side. A magnetic head is positioned along the magnetic tape transport path from the cassette to the take-up reel. Magnetic tape feeding and winding occur between the reel on the cassette side (feed reel) and the reel on the magnetic recording and playback device side (take-up reel). During this process, the magnetic head contacts and slides against the surface of the magnetic layer side of the magnetic tape, thereby recording and / or reproducing data. In contrast, in a double-reel cassette, both the feed reel and the take-up reel are located inside the cassette. The aforementioned magnetic tape cassette can be either a single-reel or a double-reel type. The aforementioned magnetic tape cassette may include the magnetic tape involved in one aspect of the present invention; other types may utilize known technologies.
[0172] [Magnetic Recording Reproduction Device] One aspect of the present invention relates to a magnetic recording and reproducing apparatus comprising the aforementioned magnetic tape.
[0173] In this invention and specification, a "magnetic recording and playback apparatus" refers to an apparatus capable of at least one of recording data onto a magnetic tape and reproducing data recorded on the magnetic tape. This apparatus is commonly referred to as a drive. The aforementioned magnetic recording and playback apparatus can, for example, be a sliding type magnetic recording and playback apparatus. A sliding type magnetic recording and playback apparatus is an apparatus in which the surface of the magnetic layer side contacts and slides against the magnetic head during data recording and / or reproduction of the recorded data on the magnetic tape. For example, the aforementioned magnetic recording and playback apparatus can detachably include the aforementioned magnetic tape cassette.
[0174] The aforementioned magnetic recording and playback apparatus may include a magnetic head. The magnetic head may be a recording head capable of recording data onto a magnetic tape, or a playback head capable of reproducing data recorded onto a magnetic tape. Furthermore, in one embodiment, the aforementioned magnetic recording and playback apparatus may include both a recording head and a playback head as a single magnetic head. In another embodiment, the magnetic head included in the aforementioned magnetic recording and playback apparatus may have a structure that incorporates both an element for recording data (recording element) and an element for reproducing data (reproduction element) within a single magnetic head. Hereinafter, the element for recording data and the element for reproducing data will be collectively referred to as "data element." As a playback head, a magnetic head (MR head) that includes a magnetoresistive (MR) element capable of reading data recorded on a magnetic tape with good sensitivity is preferred. As MR heads, various known MR heads such as AMR (Anisotropic Magnetoresistive) heads, GMR (Giant Magnetoresistive) heads, and TMR (Tunnel Magnetoresistive) heads can be used. Furthermore, the head for recording and / or reproducing data can include a servo signal readout element. Alternatively, a head equipped with a servo signal readout element (servo head) can be included in the aforementioned magnetic recording and reproducing apparatus as a separate head from the head for recording and / or reproducing data. For example, the head for recording and / or reproducing recorded data (hereinafter also referred to as a "recording and reproducing head") can include two servo signal readout elements, each capable of simultaneously reading two adjacent servo tapes. One or more data elements can be configured between the two servo signal readout elements.
[0175] In the aforementioned magnetic recording and playback apparatus, for example, data recording on the magnetic tape and / or playback of data recorded on the magnetic tape can be performed by contacting and sliding the surface of the magnetic layer side of the magnetic tape with the magnetic head. The aforementioned magnetic recording and playback apparatus only needs to include the magnetic tape involved in one aspect of the present invention; for other aspects, known techniques can be applied.
[0176] For example, when recording and / or reproducing recorded data, the first step is to track the data using a servo signal. That is, by making the servo signal read element follow a specified servo track, the data read element can be controlled to pass over the target data track. The movement of the data track is achieved by changing the servo track read by the servo signal read element along the width of the magnetic tape. Furthermore, the recording and playback head can also record and / or reproduce other data tapes. At this point, the servo signal readout element is moved to the specified servo tape using the aforementioned UDIM information, and tracking of that servo tape begins. Example
[0177] The present invention will now be described in more detail through examples. However, the present invention is not limited to the embodiments shown in the examples. Unless otherwise specified, "parts" and "%" as used below refer to "parts by mass" and "% by mass". Unless otherwise specified, the following processes and evaluations are performed in atmospheric conditions at room temperature (20-25°C). "eq" as used below refers to equivalent, which is a unit that cannot be converted to SI units.
[0178] [Strongly magnetic powder] In Table 1, "BaFe" in the "Strong Magnetic Powder" column refers to hexagonal barium ferrite powder with an average particle size (average plate diameter) of 21 nm.
[0179] In Table 1, "SrFe" listed in the "Strong Magnetic Powder" column refers to hexagonal strontium ferrite powder prepared as follows. 1707g of SrCO3, 687g of H3BO3, 1120g of Fe2O3, 45g of Al(OH)3, 24g of BaCO3, 13g of CaCO3, and 235g of Nd2O3 were weighed and mixed in a mixer to obtain a raw material mixture. The obtained raw material mixture was melted in a platinum crucible at a melting temperature of 1390°C. While stirring the melt, the melt outlet located at the bottom of the platinum crucible was heated, and the melt was discharged into a rod shape at a rate of approximately 6 g / s. The discharged melt was then rapidly cooled by rolling using water-cooled twin rollers to produce an amorphous substance. 280g of the prepared amorphous material was placed in an electric furnace and heated to 635℃ (crystallization temperature) at a heating rate of 3.5℃ / min. The temperature was then maintained at the same temperature for 5 hours to allow hexagonal strontium ferrite particles to precipitate (crystallize). Next, the crystallized material containing hexagonal strontium ferrite particles obtained above was coarsely crushed using a mortar. 1000g of 1mm zirconium oxide beads and 800mL of 1% acetic acid were added to a glass bottle containing the crushed material, and the mixture was dispersed using a paint mixer for 3 hours. The resulting dispersion was then separated from the beads and placed in a stainless steel beaker. The dispersion was allowed to stand at 100°C for 3 hours to dissolve the glass components. Afterward, the solution was centrifuged to allow precipitation, and the mixture was repeatedly decanted and washed. Finally, it was dried in a furnace at 110°C for 6 hours to obtain hexagonal strontium ferrite powder. The hexagonal strontium ferrite powder obtained above has an average particle size of 18 nm and an activation volume of 902 nm. 3 The anisotropy constant Ku is 2.2 × 10⁻⁶. 5 J / m 3 The mass magnetization σs is 49 A·m 2 / kg. A 12 mg sample powder was collected from the hexagonal strontium ferrite powder obtained above. The elemental composition of the filtrate obtained by partially dissolving the sample powder under the above-described dissolution conditions was determined by an ICP analysis device. The surface layer content of neodymium atoms was then calculated. In addition, 12 mg of sample powder was collected from the hexagonal strontium ferrite powder obtained above, and the elemental analysis of the filtrate obtained by completely dissolving the sample powder under the above-described dissolution conditions was performed using an ICP analysis device to determine the bulk content of neodymium atoms. In the hexagonal strontium ferrite powder obtained above, the content of neodymium atoms relative to 100 atomic% of iron atoms (bulk content) is 2.9 atomic%. Furthermore, the surface portion of neodymium atoms contains 8.0 atomic%. It was confirmed that the ratio of surface portion content to bulk content, "surface portion content / bulk content", is 2.8, indicating that neodymium atoms are concentrated on the surface of the particles.
[0180] The powder obtained above was confirmed to exhibit a hexagonal ferrite crystal structure by scanning CuKα rays under a voltage of 45 kV and an intensity of 40 mA, and by measuring the X-ray diffraction pattern under the following conditions (X-ray diffraction analysis). The powder obtained above exhibits a magnetoplumbite (M-type) hexagonal ferrite crystal structure. Furthermore, the crystal phase detected by X-ray diffraction analysis is a magnetoplumbite type single phase. PANalytical X'Pert Pro diffractometer, PIXcel detector Soller slit for incident and diffracted beams: 0.017 radians Fixed angle of the dispersing slit: 1 / 4 degree Mask: 10mm Scattering prevention slit: 1 / 4 degree Measurement mode: Continuous Measurement time for each stage: 3 seconds Measurement speed: 0.017 degrees per second Measurement step size: 0.05 degrees
[0181] The activation volume and anisotropy constant Ku of the hexagonal strontium ferrite powder were obtained using a vibrating sample type magnetometer (manufactured by TOEI INDUSTRY CO., LTD.) through the method described above. Furthermore, the mass magnetization σs was measured by a vibrating sample type magnetometer (manufactured by TOEI INDUSTRY CO.,LTD.) under a magnetic field strength of 1194 kA / m (15 kOe).
[0182] [Example 1] <Preparation of Alumina Dispersion A (Grinding Agent Solution)> With an α-oxidation rate of approximately 65% and a BET (Brunauer-Emmett-Teller) specific surface area of 21 m², 2 A mixture of 100.0 parts of alumina powder (HIT-80 manufactured by Sumitomo Chemical Company, Limited), 3.0 parts of 2,3-dihydroxynaphthalene (manufactured by Tokyo Chemical Company), 31.3 parts of a 32% solution of polyester polyurethane resin with SO3Na groups as polar groups (UR-4800 manufactured by TOYOBO CO.,LTD. (polar group content: 80 meq / kg)) (solvent being a mixture of methyl ethyl ketone and toluene), and 570.0 parts of a 1:1 (mass ratio) mixed solution of methyl ethyl ketone and cyclohexanone as solvents was dispersed for 5 hours using a paint mixer in the presence of zirconia beads. After dispersion, the dispersion and beads were separated using a sieve to obtain an alumina dispersion. Next, the alumina dispersion was placed in a flow centrifuge (Hitachi, Ltd. CP100WX ultracentrifuge) and classified using the following method. The viscosity of the alumina dispersion prepared above was actually measured. Based on Stokes' theorem and centrifugal theory, the rotational speed of the cylinder was adjusted according to the lower limit of the particle size range to be removed (hereinafter also referred to as "D"). In the case of alumina dispersion A used as an abrasive solution in Example 1, D was set to 130 nm. To remove particles with a diameter greater than 130 nm, centrifugal separation was performed at 6000 G. 1 G = 9.80665 m / s 2 The supernatant obtained after 1 hour of centrifugation was designated as alumina dispersion A. The solid content concentration of alumina dispersion A was adjusted to 12% using a 1:1 (mass ratio) mixture of methyl ethyl ketone and cyclohexanone.
[0183] <Formulation of the composition for forming a magnetic layer> (Magnetic fluid) Strongly magnetic powder (refer to Table 1): 100.0 parts Vinyl chloride copolymer containing SO3Na groups: 10.0 parts Weight-average molecular weight: 70,000, SO3Na group: 0.2 meq / g Polyurethane resin containing SO3Na groups: 4.0 parts Weight-average molecular weight: 70,000, SO3Na group: 0.2 meq / g Cyclohexanone: 150.0 parts Methyl ethyl ketone: 170.0 parts (Grinding agent solution) Alumina dispersion A: 50.0 parts (6.0 parts as a grinding agent (solid component)) (Other ingredients) Carbon black: 0.5 parts Average particle size: 80nm Stearic acid: 1.0 part Stearamide: 0.3 parts Butyl stearate: 6.0 parts Polyisocyanate (CORONATE manufactured by TOSOH CORPORATION (registered trademark)): 2.5 parts (Adding solvents during finishing) Cyclohexanone: 300.0 parts Methyl ethyl ketone: 140.0 parts
[0184] <Formulation of the composition for forming a non-magnetic layer> Non-magnetic inorganic powder (α-iron oxide): 100.0 parts Average particle size (average major axis length): 0.15 μm, average needle-like ratio: 7, BET specific surface area: 52 m² 2 / g Carbon black: 30.0 parts Average particle size: 20nm Vinyl chloride copolymer containing SO3Na groups: 20.0 parts Weight-average molecular weight: 70,000, SO3Na group: 0.2 meq / g Polyurethane resin containing SO3Na groups: 100.0 parts Weight-average molecular weight: 70,000, SO3Na group: 0.2 meq / g Trioctylamine: 1.0 part Phenylophosphonic acid: 4.0 parts Stearic acid: 1.0 part Stearamide: 0.3 parts Butyl stearate: 3.0 parts Cyclohexanone: 450.0 parts Methyl ethyl ketone: 450.0 parts
[0185] <Formulation of the composition for forming the back coating> Carbon black: 100.0 parts Average particle size: 40nm, DBP (Dibutyl phthalate) oil absorption: 74cm³ 3 / 100g Copper phthalocyanine: 3.0 parts Nitrocellulose: 25.0 parts Polyester polyurethane resin containing sulfonic acid groups (UR-8401 manufactured by TOYOBO CO., LTD.): 60 parts Polyester resin (Vylon 500 manufactured by Toyobo Co., Ltd.): 4.0 parts Alumina powder (specific surface area 17m²) 2 / g of α-alumina): 1.0 part Polyisocyanate (Takenate D-101E manufactured by Mitsui Chemicals, Inc.): 15.0 parts Methyl ethyl ketone: 600.0 parts Toluene: 600.0 parts
[0186] <Preparation of the composition for forming each layer> The composition for forming magnetic layers was prepared by the following method. The various components of the above magnetic fluid were mixed using a homogenizer, and then the magnetic fluid was prepared by bead dispersion for 10 minutes using zirconia beads with a diameter of 0.05 mm in a continuous horizontal bead mill. Using the aforementioned bead mill, the magnetic fluid, the aforementioned abrasive fluid, other components, and finishing additives were mixed and then treated with an intermittent ultrasonic device (20 kHz, 300 W) for 0.5 minutes (ultrasonic dispersion). The mixture was then filtered using a filter with a pore size of 0.5 μm to prepare a composition for forming a magnetic layer. The composition for forming a nonmagnetic layer was prepared by the following method. A dispersion was obtained by dispersing all components except stearic acid and butyl stearate for 12 hours using an intermittent vertical sand mill. Zirconia beads with a diameter of 0.1 mm were used as dispersion beads. The remaining components were then added to the obtained dispersion and stirred using a disperser. The resulting dispersion was filtered through a filter with a pore size of 0.5 μm, thereby preparing a composition for forming a non-magnetic layer. The composition for forming a back coating was prepared by the following method. The above-mentioned components, excluding polyisocyanate, were introduced into a dissolver mixer and stirred at a circumferential speed of 10 m / s for 30 minutes. Dispersion was then performed using a horizontal bead mill disperser. Polyisocyanate was then added, and the mixture was stirred and mixed using a dissolver mixer to prepare a composition for forming a back coating.
[0187] <The Making of Cassette Tapes> A non-magnetic layer was formed by coating a non-magnetic layer forming composition onto the surface of a 3.6 μm thick polyethylene naphthalate support to a thickness of 0.7 μm after drying and then allowing it to dry. A magnetic layer forming composition was then coated onto the surface of the formed non-magnetic layer to a thickness of 70 nm after drying, thus forming a coating layer. While the coating layer was still undried, a magnetic field of 0.4 T was applied perpendicularly to the surface of the coating layer to perform a vertical orientation treatment, and then the coating layer was allowed to dry. Then, on the surface of the polyethylene naphthalate support opposite to the surface where the non-magnetic layer and the magnetic layer are formed, the back coating composition is applied to a thickness of 0.3 μm after drying and then dried. Then, the surface was smoothed (calendering) by passing it through a calendering roll made of only metal rolls at a speed of 100 m / s, a linear pressure of 300 kg / cm (294 kN / m), and a calendering temperature of 100°C (the surface temperature of the calendering roll). Then, after heat treatment at an ambient temperature of 70°C for 36 hours, the magnetic tape was cut into 1 / 2-inch (0.0127-meter) widths. The thickness of each of the above layers is the design thickness calculated based on manufacturing conditions.
[0188] [Examples 2-13, Comparative Examples 1-4] The items shown in Table 1 were changed as shown in Table 1, except that the magnetic tape was made using the method described in Example 1. Regarding Examples 9-12, a fluorinated compound was added to the formulation of the magnetic layer forming composition. The added fluorinated compound was a fluorinated polystyrene derivative containing a crosslinking group, which contained 1% by mass and 99% by mass of the repeating unit represented by the formula [1-2] as described above, and 1% by mass and 95% by mass of the repeating unit containing a crosslinking group. The repeating unit containing the crosslinking group had an epoxy group as a crosslinking group. In detail, when preparing the magnetic liquid, a commercially available additive containing the fluorinated polystyrene derivative containing the crosslinking group (Neo Fluoripale "NFR-325" manufactured by NODA SCREEN CO., LTD.) was used so that the amount of the above-mentioned additive relative to 100.0 parts of the strong magnetic powder contained in the magnetic layer forming composition was the value shown in Table 1. Regarding Comparative Example 3, no fractionation was performed in the preparation of alumina dispersion A (grinding solution).
[0189] [Table 1]
[0190] [Evaluation Method] <Standard deviation of guide roller friction> For each of Examples 1-13 and Comparative Examples 1-4, a piece of magnetic tape approximately 100m in length was cut from the magnetic tape produced above and wound around it. Figure 1 The feed roller 1 of the roll-to-roll measuring instrument with the structure shown is wound in such a way that the back coating of the magnetic tape comes into contact with the guide rollers 5 and 6. Then, the standard deviation of the guide roller friction force is determined by the method described above.
[0191] <Surface area ratio of bright areas above 140nm in SEM> For each of Examples 1-13 and Comparative Examples 1-4, a section of magnetic tape prepared as described above was used as the test sample. A Hitachi, Ltd. FE-SEM S4800 was used as the FE-SEM, and the surface area ratio of bright areas above 140 nm was determined using the method described above. ImageJ was used as the image analysis software. Denoising was performed using the following method: In the ImageJ image analysis software, the Despeckle denoising process was selected, and noise components were removed.
[0192] <Total thickness of magnetic tape> For each of Examples 1-13 and Comparative Examples 1-4, ten 5cm long test specimens were cut from the magnetic tape prepared above, and the thickness was measured by overlapping these test specimens. The thickness was measured using a digital thickness gauge with a Millimar 1240 compact amplifier and a Millimar 1301 inductive probe manufactured by MARH. The total thickness of the magnetic tape was obtained by dividing the measured thickness by 10 (the thickness of each test specimen). In Examples 1-13 and Comparative Examples 1-4, the total thickness of the magnetic tape was 4.7μm.
[0193] <Vertical Rectangular Ratio> For each of Examples 1-13 and Comparative Examples 1-4, three test specimens with a short side of 12 mm and a long side of 32 mm were cut from the magnetic tape prepared above. Each test specimen was folded once along the short side and twice along the long side to a size of 6 mm × 8 mm. The three test specimens folded in this way were overlapped and placed inside a vibrating test specimen type magnetometer. The three test specimens were overlapped in such a way that the orientation of each test specimen (the length direction and the width direction of the test specimen) was consistent. Using a TEM-WF82.5R-152 vibrating sample magnetometer manufactured by TOEI INDUSTRY CO.,LTD., hysteresis curves (MH curves) were obtained by scanning an external magnetic field at a measurement temperature of 24°C. To obtain the vertical MH curve, the test specimen was positioned on the vibrating sample magnetometer with the magnetic field direction orthogonal to the surface of the test specimen. Regarding the external magnetic field scanning, the scanning conditions shown in Table 2 were followed, with the average value at each step set to 1. The scan started at a magnetic field strength of 1197 kA / m, proceeded to -1197 kA / m, and then back to 1197 kA / m. The scanning conditions shown in Table 2 were implemented sequentially from top to bottom. The total scanning time was 312 seconds. Furthermore, the magnetization of only the test specimen probe was measured beforehand and subtracted as background noise during the measurement. For each test specimen, the saturation magnetization calculated from the vertical MH curve obtained in this way was all within 5 × 10⁻⁶. -6 ~10×10 -6 A·m 2 (5×10) -3 ~10×10 -3 Within the range of emu). The vertical rectangularity ratio of each magnetic tape was determined based on the vertical MH curve obtained through the above measurements.
[0194] [Table 2]
[0195] <ΔσPES> In an environment with a temperature of 20–25°C and a relative humidity of 40–60%, an LTO-G (Generation) 9 driver was used as the evaluation driver. The drive tension was set to 0.6N and the tape was run for 10,000 cycles. Then, the drive tension was set to 1.3N and the tape was run for 200 cycles, followed by a drive tension of 0.4N and another 200 cycles. The difference between the maximum σPES value during the 200 cycles at 0.4N and the maximum σPES value during the 1.3N cycle (calculated using the following formula) is defined as ΔσPES. σPES was determined by analyzing the driver's dump file. ΔσPES = (Maximum σPES in 200 passes of 0.4N downstrip) - (Maximum σPES in 1.3N downstrip) It can be said that the smaller the value of ΔσPES obtained in this way, the less PES changes. Regarding Comparative Example 1, since the conveyor belt was stopped midway, ΔσPES could not be calculated.
[0196] <Coefficient of Friction> For each of Examples 1 to 13 and Comparative Examples 1 to 4, a test sample was cut from the magnetic tape prepared above. On an AlTiC (alumina-titanium carbide) rod with an arithmetic mean roughness Ra of 15 nm and a diameter of 4 mm in a 40 μm × 40 μm area measured by atomic force microscopy (AFM), a magnetic tape (sample for measurement) was wound around the rod with its width direction parallel to the axial direction of the rod and the magnetic layer surface in contact with the rod. A 100 g weight was suspended from one end of the tape at a wrap angle of 20°, and the other end was mounted to a force sensor. The tape was slid at a speed of 14 mm / s, with each pass being 45 mm, for a total of 100 passes. The load during the first and 100th passes was measured using a force sensor, and the measured values were obtained according to the following formula: Coefficient of friction = ln(measured value (g) / 100 (g)) / 0.349 The coefficients of friction for the 1st and 100th passes were calculated (the denominator of the formula is the value after converting the 20° wrap angle to radians). The measurement environment was set as a low-temperature, high-humidity environment that is considered to have the highest coefficient of friction in the environment guaranteed by LTO (Linear Tape-Open) actuators, specifically an environment with a temperature of 13°C and a relative humidity of 80%. Regarding the evaluation results, if adhesion between the magnetic layer surface of the magnetic tape and the aforementioned round rod occurs during the measurement, making it impossible to evaluate the coefficient of friction, the evaluation result is set to "D". Furthermore, the coefficient of friction equivalent to the upper limit of the force sensor's measurement is 0.80, therefore, a coefficient of friction exceeding 0.80 cannot be measured. If the coefficient of friction exceeds the upper limit of the force sensor's measurement, the evaluation result is set to "C". If the coefficient of friction is less than 0.6, the evaluation result is set to "A", and if the coefficient of friction is 0.6 or higher but less than 0.80, the evaluation result is set to "B". Magnetic tapes with evaluation results of A or B can display a low coefficient of friction for the magnetic head, and are therefore preferred.
[0197] The results are shown in Table 3.
[0198] [Table 3]
[0199] Based on the results shown in Table 3, it can be confirmed that the variation in PES is small in the magnetic tapes of Examples 1 to 13. Furthermore, based on the results shown in Table 3, it can also be confirmed that the magnetic tapes of Examples 1 to 13 are magnetic tapes capable of exhibiting a low coefficient of friction for the magnetic head. Industrial availability
[0200] This invention is useful in the technical field of magnetic tapes, such as for data storage purposes.
Claims
1. A magnetic tape having a non-magnetic support and a magnetic layer containing strongly magnetic powder, wherein, The standard deviation of the friction force determined by measuring the friction force between the surface of the magnetic layer and the guide roller of the LTO driver is greater than 0.35N and less than 0.70N.
2. The magnetic tape according to claim 1, wherein, The area fraction of multiple bright regions with an equivalent circle diameter of 140 nm or more in the binarized image of the secondary electron image obtained by scanning electron microscopy at an accelerating voltage of 5 kV on the surface of the magnetic layer is 0.010% or more and 0.100% or less.
3. The magnetic tape according to claim 1, wherein, The standard deviation of the frictional force is greater than 0.45N and less than 0.70N.
4. The magnetic tape according to claim 1, wherein, The vertical rectangularity ratio of the magnetic tape is 0.65 or higher.
5. The magnetic tape according to claim 1, wherein, Between the non-magnetic support and the magnetic layer, there is also a non-magnetic layer containing non-magnetic powder.
6. The magnetic tape according to claim 1, wherein, The non-magnetic support also has a back coating containing non-magnetic powder on the side opposite to the side with the magnetic layer.
7. The magnetic tape according to claim 1, wherein, The total thickness of the magnetic tape is less than 5.0 μm.
8. The magnetic tape according to claim 1, wherein, The non-magnetic support is a polyester support.
9. The magnetic tape according to claim 1, wherein, The strongly magnetic powder is hexagonal ferrite powder.
10. The magnetic tape according to claim 9, wherein, The hexagonal ferrite powder is hexagonal barium ferrite powder.
11. The magnetic tape according to claim 9, wherein, The hexagonal ferrite powder is hexagonal strontium ferrite powder.
12. The magnetic tape according to claim 1, wherein, In the binarized image of the secondary electron image obtained by scanning electron microscopy at an accelerating voltage of 5 kV on the surface of the magnetic layer, the area fraction of multiple bright regions with an equivalent circle diameter of 140 nm or more is 0.010% or more and 0.100% or less. The standard deviation of the frictional force is greater than 0.45N and less than 0.70N. The vertical rectangle ratio of the magnetic tape is 0.65 or higher. Between the non-magnetic support and the magnetic layer, there is also a non-magnetic layer containing non-magnetic powder. The non-magnetic support also has a back coating containing non-magnetic powder on the surface opposite to the surface with the magnetic layer. The total thickness of the magnetic tape is less than 5.0 μm. The non-magnetic support is a polyester support. The strongly magnetic powder is selected from the group consisting of hexagonal barium ferrite and hexagonal strontium ferrite powders.
13. A magnetic tape cassette comprising the magnetic tape according to any one of claims 1 to 12.
14. A magnetic recording and reproducing apparatus comprising the magnetic tape according to any one of claims 1 to 12.
Citation Information
Patent Citations
Magnetic recording medium
JP1988090023A
Electric cleaner
JP1988130030A
Paper feeder
JP1988300032A
Production of magnetic paint
JP1989079274A
Production of kneading substance for magnetic coating
JP1989106338A
